Conductive elastic roller, method for manufacturing the same, process cartridge, and electrophotographic image forming apparatus

CN122958741APending Publication Date: 2026-10-23CANON KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610520511.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-22
Filing Date
2026-04-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]然而,已经发现根据日本特开2020-117578号公报的离子导电型发泡导电性弹性辊以及根据日本特开2016-126332号公报的电子照相构件特别是在低温低湿环境下长时间操作时难以在长期使用中维持初始操作阶段中的低电阻特性

Benefits of technology

[0049]根据本公开的至少一个方面,可以提供一种导电性弹性辊,其即使在低温低湿环境下长时间操作时也抑制电阻值的增加,并有助于形成高品质的电子照相图像。另外,根据本公开的至少一个方面,可以提供一种导电性弹性辊的制造方法,所述导电性弹性辊即使在低温低湿环境下长时间操作时也抑制电阻值的增加,并有助于形成高品质的电子照相图像。此外,根据本公开的至少一个方面,可以提供一种使用上述导电性弹性辊并有助于形成高品质的电子照相图像的处理盒和电子照相图像形成设备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958741A_ABST
    Figure CN122958741A_ABST
Patent Text Reader

Abstract

This invention relates to a conductive elastic roller, a method for manufacturing the same, a processing cartridge, and an electrophotographic image forming apparatus. A conductive elastic roller comprises a conductive substrate and a conductive elastic layer on the substrate. The conductive elastic layer comprises a polyurethane containing urethane bonds and ether bonds, and an anion. The polyurethane comprises at least one selected from a specific cationic structure. The anion comprises at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion. The sum of the alkali metal content and the alkaline earth metal content in the conductive elastic layer is 1.0 × 10⁻⁶. ‑6 Below mol / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a conductive elastic roller and a method for manufacturing the same, a processing box, and an electrophotographic image forming apparatus. Background Technology

[0002] There is a need to further improve the processing speed, compatibility with various media, durability for long-term use, and compatibility with various environments of electrophotographic image forming equipment. As conductive elastic rollers for electrophotographic image forming equipment, conductive elastic rollers that utilize electron conductivity by using low-resistance fillers to achieve conductivity, conductive elastic rollers that utilize ionic conductivity by using binders and ionic compounds, and conductive elastic rollers constructed using these components together are widely known.

[0003] In many cases, ion-conductive conductive elastic rollers are suitable for electrophotographic image forming equipment that performs high-resolution image formation due to their excellent uniform resistance distribution. On the other hand, it is known that when a voltage is applied to an ion-conductive conductive elastic roller, ions move within the binder of the conductive elastic roller due to the influence of the voltage, and as a result, the resistance may increase significantly due to prolonged voltage application.

[0004] Japanese Patent Application Publication No. 2020-117578 discloses an ion-conductive foamed conductive elastic roller that exhibits excellent performance even during long-term operation in high-temperature and high-humidity environments with minimal increase in resistance.

[0005] Japanese Patent Application Publication No. 2016-126332 discloses an electrophotographic component that has a charge supply capability that does not deteriorate even after long-term storage and use in high temperature and high humidity environments, and helps to form high-quality electrophotographic images.

[0006] There is a need for electrophotographic image forming equipment with improved processing speed and longer lifespan, which is required to stably form excellent electrophotographic images.

[0007] However, it has been found that the ion-conductive foamed conductive elastic roller according to Japanese Patent Application Publication No. 2020-117578 and the electrophotographic component according to Japanese Patent Application Publication No. 2016-126332 are particularly difficult to maintain the low resistance characteristics of the initial operation stage during long-term use, especially when operating for a long time in low temperature and low humidity environments.

[0008] In other words, when ion-conductive conductive elastic rollers operate for extended periods in low-temperature and low-humidity environments, it is difficult to suppress the increase in resistance and may be difficult to stably form high-quality electrophotographic images. Summary of the Invention

[0009] This disclosure aims to provide a conductive elastic roller that suppresses the increase in resistance even during prolonged operation in low-temperature and low-humidity environments, thereby contributing to the formation of high-quality electrophotographic images. Furthermore, this disclosure aims to provide a method for manufacturing a conductive elastic roller that suppresses the increase in resistance even during prolonged operation in low-temperature and low-humidity environments, thereby contributing to the formation of high-quality electrophotographic images. Additionally, this disclosure aims to provide a processing box and an electrophotographic image forming apparatus that utilize the aforementioned conductive elastic roller and contribute to the formation of high-quality electrophotographic images.

[0010] According to at least one aspect of this disclosure, a conductive elastic roller is provided, comprising:

[0011] A conductive substrate; and a conductive elastic layer on the substrate, wherein...

[0012] The conductive elastic layer comprises polyurethane containing urethane bonds and ether bonds, and anionic compounds.

[0013] The polyurethane includes at least one of the following: a cationic structure represented by the following structural formula (1), a cationic structure represented by the following structural formula (2), and a cationic structure represented by the following structural formula (3).

[0014] The anion includes at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion, and

[0015] The sum of the alkali metal content and the alkaline earth metal content in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g:

[0016]

[0017] In structural formula (1), R1 and R2 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 5-membered ring together with each nitrogen atom bonded to R1 and R2, and d1 represents an integer of 0 or 1. Z1 to Z3 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms. However, at least one of Z1 to Z3 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103):

[0018]

[0019] In structural formula (2), R3 and R4 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 6-membered ring together with each nitrogen atom bonded to R3 and R4, d2 represents an integer greater than or less than 0 and less than 2, and Z5 may be the same or different when d2 is 2. Z4 and Z5 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group with 1 or more hydrogen atoms and less than 4 carbon atoms. However, at least one of Z4 and Z5 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103):

[0020]

[0021] In structural formula (3), R5 represents the hydrocarbon group required to form a nitrogen-containing heteroaromatic ring together with the nitrogen atom bonded to R5, and d3 represents an integer of 0 or 1. Z6 and Z7 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group with 1 or more hydrogen atoms and 4 or fewer carbon atoms. However, at least one of Z6 and Z7 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103):

[0022]

[0023] In structural formulas (Z101), (Z102), and (Z103), R101, R102, and R103 each independently represent a straight-chain or branched divalent hydrocarbon group. The symbol "*" indicates a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic 5-membered ring constituting structural formula (1), a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic 6-membered ring constituting structural formula (2), or a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic ring constituting structural formula (3). The symbol "**" indicates a bonding portion with a carbon atom in the polymer chain of the polyurethane.

[0024] According to at least one aspect of this disclosure, a method for manufacturing a conductive elastic roller is provided.

[0025] The conductive elastic roller includes a conductive substrate and a conductive elastic layer on the substrate;

[0026] The conductive elastic layer comprises polyurethane containing urethane bonds and ether bonds, as well as anionic compounds.

[0027] The polyurethane comprises a cationic structure represented by the above structural formula (1).

[0028] The anion includes at least one selected from bis(fluorosulfonyl)imide anion and bis(fluorosulfonate)imide anion.

[0029] The sum of the alkali metal content and the alkaline earth metal content in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g;

[0030] The manufacturing method includes:

[0031] The step of injecting the elastic layer forming material into a mold in which the substrate is disposed; and

[0032] The steps of heating the mold and curing the elastic layer forming material to form the conductive elastic layer, wherein...

[0033] The elastic layer forming material comprises at least a liquid composition containing an ionic compound represented by the following structural formula (7), a polyol, and a polyisocyanate.

[0034] The liquid composition contains 95% by mass or more and less than 100% by mass of the ionic compound.

[0035] The liquid composition contains alkali metals and alkaline earth metals at a concentration of less than 30,000 ppm, and

[0036] The viscosity of the liquid composition at 23°C is 1~1000 mPa·s.

[0037]

[0038] In structural formula (7), R9 and R10 each independently represent an alkyl group having 1 or more but less than 4 carbon atoms, a hydroxyalkyl group having 1 or more but less than 4 carbon atoms, or a hydrogen atom; at least one of R9 and R10 is a hydroxyalkyl group having 1 or more but less than 4 carbon atoms. - It represents anion.

[0039] According to at least one aspect of this disclosure, a processing cartridge is provided, configured to be detachably mounted to the body of an electrophotographic image forming apparatus, the processing cartridge comprising:

[0040] When the processing box is installed onto the main body, it is a contact member that is electrically connected to the electrical contact point of the main body;

[0041] The developing roller; and the developing agent supply roller for supplying developing agent to the developing roller, wherein...

[0042] The processing cartridge is configured such that a voltage can be applied between the developing roller and the developer supply roller via an electrical connection to the main body, and

[0043] The developer supply roller is the aforementioned conductive elastic roller.

[0044] According to at least one aspect of this disclosure, an electrophotographic image forming apparatus is provided, comprising at least:

[0045] Electrophotographic photosensitive components;

[0046] A developing roller disposed in contact with the electrophotographic photosensitive component; and

[0047] A developer supply roller that supplies developer to the developing roller, wherein

[0048] The developer supply roller is the aforementioned conductive elastic roller.

[0049] According to at least one aspect of this disclosure, a conductive elastic roller can be provided that suppresses the increase in resistance value even during prolonged operation in a low-temperature and low-humidity environment, and contributes to the formation of high-quality electrophotographic images. Additionally, according to at least one aspect of this disclosure, a method for manufacturing a conductive elastic roller can be provided, wherein the conductive elastic roller suppresses the increase in resistance value even during prolonged operation in a low-temperature and low-humidity environment, and contributes to the formation of high-quality electrophotographic images. Furthermore, according to at least one aspect of this disclosure, a processing box and an electrophotographic image forming apparatus using the aforementioned conductive elastic roller and contributing to the formation of high-quality electrophotographic images can be provided.

[0050] The features of this disclosure will become apparent from the following description of the embodiments with reference to the accompanying drawings. The following description of the embodiments is illustrated by way of example. Attached Figure Description

[0051] Figure 1 This is a schematic cross-sectional view of a conductive elastic roller.

[0052] Figure 2 This is a schematic diagram of an electrophotographic image forming device.

[0053] Figure 3 This is a schematic diagram of the processing box.

[0054] Figure 4A and Figure 4B This is a schematic diagram of a fixture used to evaluate the resistance value of a conductive elastic roller. Detailed Implementation

[0055] In this disclosure, the expressions "from XX to YY" or "XX to YY" represent a range of values, which, unless otherwise specified, means a range of values ​​including both a lower and upper limit as endpoints. Furthermore, when a range of values ​​is described stepwise, the upper and lower limits of each range can be arbitrarily combined. In this disclosure, descriptions such as "selected from at least one of XX, YY, and ZZ" mean any of XX, YY, ZZ, combinations of XX and YY, combinations of XX and ZZ, combinations of YY and ZZ, and combinations of XX, YY, and ZZ. Here, when XX is a group, multiple XXs can be selected, and the same applies to YY and ZZ.

[0056] In ion-conductive conductive elastic rollers, during prolonged operation, ionic compounds migrate within the binder, such as polyurethane, due to the influence of applied voltage, potentially increasing the resistance. In low-resistance ion-conductive conductive elastic rollers, the migration speed of ionic compounds within the binder may increase, further increasing the resistance. This increase in resistance during prolonged operation in low-temperature, low-humidity environments, where resistance is likely to rise, is particularly difficult to suppress.

[0057] As a result of research conducted by the inventors, it has been found that in order to maintain a low resistance value in the ion-conductive conductive elastic roller during long-term use, it is important to meet the following requirements (1) and (2).

[0058] (1) Increase the dissociation rate between anions and cations constituting ionic compounds, and increase the amount of anions and cations in the binder.

[0059] (2) Restrict the migration of anions in the adhesive.

[0060] By satisfying requirement (1), the amount of electron-carrying anions in the adhesive of the conductive elastic layer, which serves as a carrier, increases, thereby reducing the initial resistance value.

[0061] On the other hand, when anions are in a state where they can easily move within the adhesive, the amount of anions capable of transporting electrons may decrease over time, and the resistance value may increase over time. Therefore, it is important to limit the migration of anions in the adhesive. In other words, by satisfying the above requirement (2), the increase in resistance value after prolonged use can be suppressed.

[0062] For the reasons stated above, it was found that by satisfying requirements (1) and (2), the low resistance value can be maintained for a long time, even during long-term operation of the ion-conductive conductive elastic roller.

[0063] The implementation scheme of this disclosure will be described in detail below.

[0064] The conductive elastic roller comprises a conductive substrate and a conductive elastic layer on the substrate. The conductive elastic layer comprises polyurethane containing urethane bonds and ether bonds, as well as anionic polymers.

[0065] The conductive elastic layer uses polyurethane containing urethane and ether bonds as a binder. Polyurethane containing urethane and ether bonds has excellent elasticity. In addition, the polymer chains in the polyurethane form hydrogen bonds through the contained ether bonds. Hydrogen bonds can restrict the migration of anions. As a result, the above requirements (2) can be met.

[0066] The polyurethane contained in the conductive elastic layer has at least one of the cationic structure represented by the above structural formula (1), the cationic structure represented by the above structural formula (2), and the cationic structure represented by the above structural formula (3).

[0067] In the cation structures represented by structural formula (1), (2), and (3), the positive charge of the cation structure has a low electron density due to the electronic conjugation of the nitrogen-containing aromatic ring. Therefore, the ionic bonding between the negative charge of the anion and the positive charge of the cation structure may be weakened, and the dissociation rate between the anion and the cation structure can be increased to meet the above requirement (1). As a result, the anion and cation responsible for conductivity are likely to move in a dissociated state, and the conductivity is unlikely to decrease even during long-term operation, and the increase in resistance can be suppressed.

[0068] The anions contained in the conductive elastic layer include at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion.

[0069] These anions have relatively large differences in solubility parameters compared to the polyurethanes containing urethane and ether bonds described above. Although the anions migrate in the polyurethane acting as a binder due to the influence of voltage applied to the conductive elastic roller, the relatively large difference in solubility parameters compared to polyurethane limits the migration of anions even during long-term operation. As a result, the above requirements (2) can be met.

[0070] Furthermore, the sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g. By meeting the above range, the low resistance characteristic of the conductive elastic roller can be maintained during long-term use.

[0071] According to the research conducted by the inventors, alkali metals and alkaline earth metals tend to inhibit the formation of hydrogen bonds between the polymer chains of polyurethane by coordinating with the ether bonds present in the polyurethane. Therefore, assuming that the content of alkali metals and alkaline earth metals in the conductive elastic layer is high, anions can move freely in the binder when a voltage is applied to the conductive elastic roller, and it becomes difficult to maintain a low resistance value during long-term operation.

[0072] By ensuring that the sum of the alkali metal content and the alkaline earth metal content in the conductive elastomer layer is 1.0 × 10⁻⁶ -6 Below mol / g, the migration of anions in polyurethane can be restricted within an appropriate range without inhibiting the formation of hydrogen bonds between polymer chains of polyurethane with ether bonds. As a result, the above requirement (2) can be met.

[0073] In this way, the configuration of this disclosure can simultaneously achieve the above-mentioned requirements (1) and (2). Specifically, by satisfying the above-mentioned requirements (1) and (2), a state in which cations and anions are unlikely to dissociate and a state in which anions are unlikely to move in the binder can be simultaneously achieved. Therefore, the increase in the resistance value of the conductive elastic roller can be suppressed, and even during long-term operation in a low-temperature and low-humidity environment where the resistance value may increase, the low resistance value at the initial stage of use can be stably maintained, thus obtaining a conductive elastic roller capable of forming high-quality images.

[0074] conductive elastic roller

[0075] The conductive elastic roller includes a conductive substrate and a conductive elastic layer on the substrate.

[0076] Foamed conductive elastic roller

[0077] The conductive elastic layer can be a foamed conductive elastic layer of foam. The conductive elastic roller can be a foamed conductive elastic roller comprising a conductive substrate and a foamed conductive elastic layer on the substrate.

[0078] The composition of the conductive elastic roller will be described.

[0079] An example of a conductive elastic roller is shown in Figure 1 . Figure 1 The conductive elastic roller 1 shown includes a conductive substrate 2 and a conductive elastic layer 3 disposed on the outer periphery of the substrate 2.

[0080] Note that the layer structure of the conductive elastic roller 1 is not limited to the configuration in which the conductive elastic layer 3 exists on the outermost surface of the conductive elastic roller 1. Examples of conductive elastic rollers 1 include conductive elastic rollers that also have a surface layer on the substrate 2 and a conductive elastic layer 3 provided on the outer periphery of the substrate 2; conductive elastic rollers that also have an elastic layer between the substrate 2 and the conductive elastic layer 3; and so on.

[0081] Conductive elastic rollers, including conductive elastic layers, can be appropriately used as charging rollers, developing rollers, toner supply rollers, etc. Conductive elastic rollers are particularly suitable for use as toner supply rollers. When the conductive elastic layer is a foamed conductive elastic layer, foamed conductive elastic rollers are particularly suitable for use as toner supply rollers.

[0082] The configuration of a conductive elastic roller according to one aspect of this disclosure will be described in detail below.

[0083] matrix

[0084] The substrate 2 is conductive and serves as a support member and electrode for the conductive elastic roller. The substrate 2 is made of, for example, a conductive material, such as a metal or alloy like aluminum, copper alloy, or stainless steel; chromium-plated or nickel-plated iron; or a conductive synthetic resin. The substrate 2 is, for example, stainless steel. The substrate 2 preferably has a solid cylindrical or hollow cylindrical shape.

[0085] The conductive elastic layer includes polyurethane containing urethane bonds and ether bonds, as well as anionic bonds.

[0086] Polyurethane has at least one cationic structure selected from the structures represented by structural formulas (1) to (3).

[0087]

[0088] In structural formula (1), R1 and R2 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 5-membered ring together with the nitrogen atoms bonded to each of R1 and R2, and d1 represents an integer of 0 or 1. Z1 to Z3 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms. However, at least one of Z1 to Z3 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103).

[0089] The hydrocarbon group having 1 or more and 4 or fewer carbon atoms is preferably an alkyl group, more preferably an alkyl group having 1 or more and 2 or fewer carbon atoms, and even more preferably an alkyl group having 2 carbon atoms. For example, the nitrogen-containing heterocyclic structure of structural formula (1) is preferably an imidazolium cation.

[0090] In structural formula (2), Z1 or Z2 is preferably represented by the structure shown in structural formula (Z101), the structure shown in structural formula (Z102), or the structure shown in structural formula (Z103). Furthermore, both Z1 and Z2 are preferably represented by the structure shown in structural formula (Z101), the structure shown in structural formula (Z102), or the structure shown in structural formula (Z103). Both Z1 and Z2 are preferably represented by the structure shown in structural formula (Z101).

[0091]

[0092] In structural formula (2), R3 and R4 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 6-membered ring together with each of the nitrogen atoms bonded to R3 and R4, d2 represents an integer greater than or less than 0 and less than 2, and Z5 may be the same or different when d2 is 2. Z4 and Z5 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and less than 4 carbon atoms. However, at least one of Z4 and Z5 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103).

[0093] The hydrocarbon group having 1 or more but less than 4 carbon atoms is preferably alkyl. For example, the nitrogen-containing heteroaromatic structure of formula (2) is preferably a pyrazine-onium cation or a pyrimidine-onium cation.

[0094]

[0095] In structural formula (3), R5 represents the hydrocarbon group required to form a nitrogen-containing heteroaromatic ring together with the nitrogen atom bonded to R5, and d3 represents an integer of 0 or 1. Z6 and Z7 each independently represent the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), the structure represented by the following structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms. However, at least one of Z6 and Z7 is the structure represented by the following structural formula (Z101), the structure represented by the following structural formula (Z102), or the structure represented by the following structural formula (Z103).

[0096] The hydrocarbon group having 1 or more but less than 4 carbon atoms is preferably alkyl. For example, the nitrogen-containing heteroaromatic structure of formula (3) is preferably a pyridinium cation.

[0097]

[0098] In structural formulas (Z101), (Z102), and (Z103), R101, R102, and R103 each independently represent a straight-chain or branched divalent hydrocarbon group. The symbol "*" indicates a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic 5-membered ring constituting structural formula (1), a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic 6-membered ring constituting structural formula (2), or a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic ring constituting structural formula (3). The symbol "**" indicates a bonding portion with a carbon atom in the polymer chain of polyurethane.

[0099] The divalent hydrocarbon group is preferably a straight-chain or branched alkylene group with 1 or more and 8 or less carbon atoms, more preferably an alkylene group with 1 or more and 4 or less carbon atoms, and even more preferably an alkylene group with 1 or more and 2 or less carbon atoms. R101, R102 and R103 are preferably -CH2-, -C2H4- or -C4H8-, and more preferably -C2H4-.

[0100] Relationship between cation structure and dissociation rate

[0101] In cases where the cationic structure of polyurethane is a structure without a nitrogen-containing aromatic ring, such as a quaternary ammonium cation or a pyrrolidine onium cation, for example, the positive charge may be located on the nitrogen atom, and the anion and cation are unlikely to dissociate.

[0102] On the other hand, when the cationic structure of polyurethane is a cationic skeleton consisting of a cationic nitrogen-containing heteroaromatic ring represented by structural formulas (1) to (3), due to the electronic conjugation of the nitrogen-containing heteroaromatic ring, the positive charge is mainly distributed on the nitrogen atom and also on other atoms on the aromatic ring. As a result, the electrostatic interaction between the cation and the anion decreases, the ionic bonding weakens, and the dissociation rate between the cation and the anion increases.

[0103] In this disclosure, the dissociation rate between cations and anions is increased by using a polyurethane with a cationic structure, wherein the cationic structure comprises a nitrogen-containing heteroaromatic ring, which is at least one selected from the structures represented by the above structural formulas (1) to (3). As a result, the amount of cations and anions that can move in the polyurethane can be increased, and the increase in the resistance value of the conductive elastic roller can be suppressed.

[0104] polyurethane

[0105] The polyurethane contained in the conductive elastic layer 3 of the conductive elastic roller has at least one cationic structure selected from the structures represented by structural formulas (1) to (3). The polyurethane contains a nitrogen-containing heteroaromatic ring structure. The polyurethane serves as a support for the anions responsible for conductivity. Note that the conductive elastic layer 3 may include a resin different from the resin having a cationic structure.

[0106] Polyurethanes having the aforementioned cationic structure are, for example, reaction products of compounds containing nitrogen-containing heteroaromatic ring structures and mixtures of polyurethane raw materials forming polyurethane. The polyurethane raw material mixture includes, for example, compounds other than compounds containing nitrogen-containing heteroaromatic ring structures (hereinafter also referred to as "nitrogen-containing heteroaromatic ring compounds"), preferably polyols and polyisocyanates. The nitrogen-containing heteroaromatic ring compounds are preferably ionic compounds containing both a nitrogen-containing heteroaromatic ring structure (which is a cation) and an anion.

[0107] Nitrogen-containing heteroaromatic ring compounds preferably have at least one functional group including a hydroxyl, amino, or glycidyl group. The hydroxyl or amino group reacts with the isocyanate group of a compound containing a cationic structure to form a bond. Therefore, nitrogen-containing heteroaromatic ring structures can be introduced into urethane molecular structures, for example, through reactions between nitrogen-containing heteroaromatic ring compounds and polyisocyanates. The glycidyl group reacts with the hydroxyl group of the nitrogen-containing heteroaromatic ring compound to form a bond. Therefore, nitrogen-containing heteroaromatic ring structures can be introduced into urethane molecular structures through reactions between nitrogen-containing heteroaromatic ring compounds and polyols.

[0108] cationic structure

[0109] Compounds containing nitrogen-containing heteroaromatic ring structures are compounds in which the portion bonded to the structure represented by structural formula (1), the structure represented by structural formula (2), and the structure represented by structural formula (3) is substituted by a functional group including a hydroxyl, amino, or glycidyl group.

[0110] The ionic compound is a precursor of at least one cationic structure selected from the structures represented by the above structural formulas (1) to (3), and can be formed, for example, by reacting with an isocyanate group or a hydroxyl group and introducing it into a polyurethane. The structures represented by structural formulas (1) to (3) will be described below.

[0111] The structure represented by structural formula (1) can be formed by a nitrogen-containing heteroaromatic 5-membered ring cation having at least one functional group including a hydroxyl, amino or glycidyl group and further including two nitrogen atoms.

[0112] In the case where the structure represented by structural formula (1) is a nitrogen-containing heteroaromatic 5-membered ring cation having at least one functional group including a hydroxyl group, it can be said that a structure having at least one structure represented by structural formula (Z101) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0113] In the case where the structure represented by structural formula (1) is a nitrogen-containing heteroaromatic 5-membered ring cation having at least one functional group including an amino group, it can be said that a structure having at least one structure represented by structural formula (Z102) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0114] This can be said when the structure represented by structural formula (1) is a nitrogen-containing heteroaromatic 5-membered ring cation having at least one functional group including a glycidyl group. In other words, by reacting an ionic compound containing a cation with a hydroxyl group, a structure having at least one structure represented by structural formula (Z103) can be obtained.

[0115] The nitrogen-containing heteroaromatic 5-membered ring in structural formula (1) is preferably imidazoline. Examples of its structure include structures having an imidazoline ring represented by the following structural formula (4):

[0116]

[0117] In structural formula (4), d1 represents an integer of 0 or 1. Z1 to Z3 each independently represent the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), the structure represented by structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms (preferably 1 to 2, more preferably 1). However, at least one of Z1 to Z3 is the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), or the structure represented by structural formula (Z103).

[0118] Examples of ionic compounds capable of forming the structure represented by structural formula (1) include the following cations having an imidazoline ring structure and a hydroxyl group:

[0119] 1-Methyl-3-hydroxymethylimidazolium cation, 1-methyl-3-(2-hydroxyethyl)imidazolium cation, 1-methyl-3-(3-hydroxypropyl)imidazolium cation, 1-methyl-3-(4-hydroxybutyl)imidazolium cation, 1-methyl-3-(6-hydroxyhexyl)imidazolium cation, 1-methyl-3-(8-hydroxyoctyl)imidazolium cation, 1-ethyl-3-(2-hydroxyethyl)imidazolium cation, 1-n-butyl-3-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(4-hydroxybutyl)imidazolium cation and 1,3-dimethyl-4-(2-hydroxyethyl)imidazolium cation;

[0120] 1,3-bis(hydroxymethyl)imidazolium cation, 1,3-bis(2-hydroxyethyl)imidazolium cation, 2-methyl-1,3-bis(hydroxymethyl)imidazolium cation, 2-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation Ions, 4-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 1,3-bis(3-hydroxypropyl)imidazolium cation, 1,3-bis(4-hydroxybutyl)imidazolium cation, 1,3-bis(6-hydroxyhexyl)imidazolium cation, 1,3-bis(8-hydroxyoctyl)imidazolium cation, 1-methyl-2,3-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,4-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,5-bis(2-hydroxyethyl)imidazolium cation;

[0121] 1,2,3-Tris(hydroxymethyl)imidazolium cation, 1,2,3-Tris(2-hydroxyethyl)imidazolium cation, 1,2,3-Tris(3-hydroxypropyl)imidazolium cation, 1,2,3-Tris(4-hydroxybutyl)imidazolium cation, 1,2,3-Tris(6-hydroxyhexyl)imidazolium cation, 1,2,3-Tris(8-hydroxyoctyl)imidazolium cation, 1,3,4-Tris(2-hydroxyethyl)imidazolium cation, 1,3,4-Tris(3-hydroxypropyl)imidazolium cation, 1,3,4-Tris(4-hydroxybutyl)imidazolium cation, 1,3,4-Tris(6-hydroxyhexyl)imidazolium cation and 1,3,4-Tris(8-hydroxyoctyl)imidazolium cation; and their derivatives.

[0122] There are no particular limitations on cations having an imidazoline ring structure and having at least one functional group including an amino or glycidyl group. Examples include cations having the following structure: wherein the hydroxyl group of the cation with the imidazoline ring structure and hydroxyl group exemplified above has been replaced by a functional group containing an amino or glycidyl group.

[0123] The structure represented by structural formula (2) can be formed by a nitrogen-containing heteroaromatic 6-membered ring cation having at least one functional group including a hydroxyl, amino or glycidyl group and further including two nitrogen atoms.

[0124] In the case where the structure represented by structural formula (2) is a nitrogen-containing heteroaromatic 6-membered ring cation having at least one functional group including a hydroxyl group, it can be said that a structure having at least one structure represented by structural formula (Z101) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0125] In the case where the structure represented by structural formula (2) is a nitrogen-containing heteroaromatic 6-membered ring cation having at least one functional group including an amino group, it can be said that a structure having at least one structure represented by structural formula (Z102) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0126] This can be said when the structure represented by structural formula (2) is a nitrogen-containing heteroaromatic 6-membered ring cation having at least one functional group including a glycidyl group. In other words, by reacting an ionic compound containing a cation with a hydroxyl group, a structure having at least one structure represented by structural formula (Z103) can be obtained.

[0127] Examples of nitrogen-containing heteroaromatic 6-membered rings in structural formula (2) include pyrimidine rings and pyrazine rings. Examples of ionic compounds capable of forming the structure represented by structural formula (2) include cations having a pyrimidine ring structure and a hydroxyl group.

[0128] 1,4-bis(2-hydroxyethyl)pyrimidine-onium cation; 1,5-bis(3-hydroxypropyl)pyrimidine-onium cation; 1-(4-hydroxybutyl)-4-(2-hydroxyethyl)pyrimidine-onium cation; 1,4-bis(2-hydroxyethyl)-2-methylpyrimidine-onium cation; and their derivatives.

[0129] There are no particular limitations on cations having a pyrimidine ring structure and having at least one functional group including an amino or glycidyl group. Examples include cations having the following structure: wherein the hydroxyl group of the cation with the pyrimidine ring structure and hydroxyl group exemplified above has been replaced by a functional group containing an amino or glycidyl group.

[0130] The structure represented by structural formula (3) can be formed by a nitrogen-containing heteroaromatic cyclic cation having at least one functional group including a hydroxyl, amino or glycidyl group and further including a nitrogen atom.

[0131] In the case where the structure represented by structural formula (3) is a nitrogen-containing heteroaromatic cyclic cation having at least one functional group including a hydroxyl group, it can be said that a structure having at least one structure represented by structural formula (Z101) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0132] In the case where the structure represented by structural formula (3) is a nitrogen-containing heteroaromatic cyclic cation having at least one functional group including an amino group, it can be said that a structure having at least one structure represented by structural formula (Z102) can be obtained by reacting an ionic compound containing a cation with an isocyanate group.

[0133] In the case where the structure represented by structural formula (3) is a nitrogen-containing heteroaromatic cyclic cation having at least one functional group including a glycidyl group, it can be said that, by reacting an ionic compound containing a cation with a hydroxyl group, a structure having at least one structure represented by structural formula (Z103) can be obtained.

[0134] Examples of nitrogen-containing heteroaromatic rings in structural formula (3) include pyrrole rings, pyridine rings, and azepine rings. Among them, pyridine rings are preferred, and the structure represented by structural formula (3) is preferably represented by the following structural formula (5).

[0135]

[0136] In structural formula (5), d3 represents an integer of 0 or 1. Z6 and Z7 each independently represent the structure represented by the above structural formula (Z101), the structure represented by the above structural formula (Z102), the structure represented by the above structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms (preferably 1 to 2, more preferably 1). However, at least one of Z6 and Z7 is the structure represented by the above structural formula (Z101), the structure represented by the above structural formula (Z102), or the structure represented by the above structural formula (Z103).

[0137] Examples of ionic compounds capable of forming the structure represented by structural formula (3) include the following cations having a pyridine ring structure and a hydroxyl group:

[0138] 1-Hydroxymethylpyridinium cation, 1-(2-hydroxyethyl)pyridinium cation, 1-(3-hydroxypropyl)pyridinium cation, 1-(4-hydroxybutyl)pyridinium cation, 1-(6-hydroxyhexyl)pyridinium cation, 1-(8-hydroxyoctyl)pyridinium cation, 2-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-methyl-1-(2-hydroxyethyl)pyridinium cation, 4-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-ethyl-1-(2-hydroxyethyl)pyridinium cation, 3-n-butyl-1-(2-hydroxyethyl)pyridinium cation Pyridinium cation, 1-methyl-2-hydroxymethylpyridinium cation, 1-methyl-3-hydroxymethylpyridinium cation, 1-methyl-4-hydroxymethylpyridinium cation, 1-methyl-2-(2-hydroxyethyl)pyridinium cation, 1-methyl-3-(2-hydroxyethyl)pyridinium cation, 1-methyl-4-(2-hydroxyethyl)pyridinium cation, 1-ethyl-3-(2-hydroxyethyl)pyridinium cation, 1-n-butyl-3-(2-hydroxyethyl)pyridinium cation, 2-methyl-4-n-butyl-1-(2-hydroxyethyl)pyridinium cation;

[0139] 1,2-bis(hydroxymethyl)pyridinium cation, 1,3-bis(hydroxymethyl)pyridinium cation, 1,4-bis(hydroxymethyl)pyridinium cation, 1,2-bis(2-hydroxyethyl)pyridinium cation, 1,3-bis(2-hydroxyethyl)pyridinium cation, 1,4-bis(2-hydroxyethyl)pyridinium cation, 1,2-bis(3-hydroxypropyl)pyridinium cation, 1,3-bis(3-hydroxypropyl)pyridinium cation, 1,4-bis(3-hydroxypropyl)pyridinium cation, 1,2-bis(4-hydroxybutyl)pyridinium cation, 1,3-bis(4-hydroxybutyl)pyridinium cation, 1,4-bis(4-hydroxybutyl)pyridinium cation Pyridium cations, 1,2-bis(6-hydroxyhexyl)pyridium cations, 1,3-bis(6-hydroxyhexyl)pyridium cations, 1,4-bis(6-hydroxyhexyl)pyridium cations, 1,2-bis(8-hydroxyoctyl)pyridium cations, 1,3-bis(8-hydroxyoctyl)pyridium cations, 1,4-bis(8-hydroxyoctyl)pyridium cations, 2-methyl-1,3-bis(2-hydroxyethyl)pyridium cations, 2-ethyl-1,3-bis(2-hydroxyethyl)pyridium cations, 5-methyl-1,3-bis(2-hydroxyethyl)pyridium cations, 5-ethyl-1,3-bis(2-hydroxyethyl)pyridium cations;

[0140] 1,2,4-Tris(hydroxymethyl)pyridinium cation, 1,2,4-tris(2-hydroxyethyl)pyridinium cation, 1,2,4-tris(3-hydroxypropyl)pyridinium cation, 1,2,4-tris(4-hydroxybutyl)pyridinium cation, 1,2,4-tris(6-hydroxyhexyl)pyridinium cation, 1,2,4-tris(8-hydroxyoctyl)pyridinium cation, 1,3,5-tris(hydroxymethyl)pyridinium cation, 1,3,5-tris(2-hydroxyethyl)pyridinium cation, 1,3,5-tris(3-hydroxypropyl)pyridinium cation, 1,3,5-tris(4-hydroxybutyl)pyridinium cation, 1,3,5-tris(6-hydroxyhexyl)pyridinium cation and 1,3,5-tris(8-hydroxyoctyl)pyridinium cation; and their derivatives.

[0141] There are no particular limitations on cations having a pyridine ring structure and having at least one functional group including an amino or glycidyl group. Examples include cations having the following structure: wherein the hydroxyl group of the cation with the pyridine ring structure and hydroxyl group exemplified above has been replaced by a functional group containing an amino or glycidyl group.

[0142] The structure represented by structural formula (Z101) is a group formed by the reaction between a hydroxyl group and an isocyanate group present in a cation. The structure represented by structural formula (Z102) is a group formed by the reaction between an amino group and an isocyanate group present in a cation. The isocyanate group reacting with the hydroxyl or amino group is preferably an isocyanate group present in a polyurethane raw material mixture, such as a polyisocyanate. The structure represented by structural formula (Z103) is a group formed by the reaction between a glycidyl group and a hydroxyl group present in a cation. The hydroxyl group reacting with the glycidyl group is preferably a hydroxyl group present in a polyurethane raw material mixture, such as a polyisocyanate.

[0143] The polyurethane preferably has the structure represented by structural formula (1) among the structures represented by structural formulas (1) to (3). Furthermore, the polyurethane preferably has the structure represented by structural formula (4) among the structures represented by structural formula (1). When the polyurethane has the structure represented by structural formula (1), the dissociation rate between the anions and cations in the polyurethane is further increased due to the chemical structure of the cation. Therefore, it is advantageous that the amount of anions and cations capable of moving in the polyurethane can be further increased, and that the increase in resistivity is more easily suppressed.

[0144] anions

[0145] The conductive elastic layer includes anions. Conductivity can be applied to the conductive elastic layer by including anions. The anions include at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion.

[0146] Anions have a relatively large difference in solubility parameters compared to polyurethane. Therefore, by using the aforementioned anions, the migration of anions in polyurethane can be limited, and the increase in resistivity during long-term operation can be suppressed.

[0147] Furthermore, due to their chemical structure, these anions are extremely chemically stable compared to halide anions, sulfate anions, and nitrate anions, and exhibit high dissociation rates with cations. Specifically, because the anions possess strong electron-withdrawing groups in their molecules to stabilize their negative charge, they exhibit high dissociation over a wide temperature range, which contributes to high conductivity over this range. Therefore, it is believed that by incorporating a conductive elastic layer containing these anions, the increase in resistance can be suppressed even during prolonged operation in low-temperature and low-humidity environments.

[0148] Specific examples of (fluorosulfonyl)imide anions include bis(fluorosulfonyl)imide anions. Specific examples of fluoroborate anions include tetrafluoroborate anions. Specific examples of fluorophosphate anions include hexafluorophosphate anions. Specific examples of (fluorosulfonate)imide anions include bis(fluorosulfonate)imide anions.

[0149] These anions preferably include bis(fluorosulfonyl)imide anions. The anions preferably include at least bis(fluorosulfonyl)imide anions. When using bis(fluorosulfonyl)imide anions, the difference in solubility parameters with polyurethanes having ether bonds can be easily controlled within an appropriate range. As a result, it becomes easier to limit the migration of anions and suppress the increase in resistivity, which is advantageous.

[0150] The anion preferably includes at least one selected from bis(fluorosulfonyl)imide anion, tetrafluoroborate anion, hexafluorophosphate anion, and bis(fluorosulfonate)imide anion. More preferably, the anion includes at least one selected from bis(fluorosulfonyl)imide anion and bis(fluorosulfonate)imide anion.

[0151] Polyurethane raw material mixture

[0152] The conductive elastic layer of the conductive elastic roller comprises polyurethane containing urethane bonds and ether bonds, as well as anionic polymers. Thermosetting polyether polyurethane is preferred because it also possesses flexibility.

[0153] While there are no particular limitations on the methods for obtaining polyurethanes having cationic structures represented by structural formulas (1) to (3), polyurethanes can be obtained, for example, by reacting a compound having at least one functional group including a hydroxyl, amino, or glycidyl group with a polyol and an isocyanate.

[0154] There are no particular restrictions on polyols, and polyols can be appropriately selected and used from a variety of polyols known as raw materials for polyurethanes.

[0155] For example, a suitable polyol can be selected and used from known polyols such as polyether polyols and polyester polyols commonly used in the manufacture of flexible polyurethane foams. One polyol can be used, or two or more polyols can be used in combination.

[0156] Note that among the polyols mentioned above, polyether polyols are suitable for manufacturing soft, highly elastic polyurethane foams with excellent resistance to damp heat and humidity. For example, polyoxyethylene oxypropylene ether triols or polyethylene propylene ester polyols are preferred.

[0157] The number-average molecular weight of the polyol is preferably 1,000 to 10,000, more preferably 1,500 to 8,000, and even more preferably 2,000 to 6,000. By ensuring that the number-average molecular weight of the polyol falls within the above range, it is easy to control the elasticity of the flexible polyurethane foam to an appropriate range, and also to control the elasticity of the foaming roller to an appropriate range. Furthermore, two or more polyols with different number-average molecular weights can be used in combination.

[0158] Polyisocyanates can be appropriately selected from a variety of polyisocyanates known as raw materials for polyurethanes and used.

[0159] Examples include 2,4- and 2,6-toluene diisocyanate (TDI), benzyl toluidine diisocyanate (TODI), naphthalene diisocyanate (NDI), diphenylmethylene diisocyanate (XDI), 4,4'-diphenylmethane diisocyanate (MDI), carbodiimide-modified MDI, polymethylene polyphenyl polyisocyanate, and polymerized polyisocyanates. These polyisocyanates can be used alone or in combination of two or more.

[0160] Note that isocyanate-terminated prepolymers obtained by reacting polyisocyanates with one or more known active hydrogen compounds can also be used as polyisocyanates.

[0161] It is preferable to mix polyols and polyisocyanates such that the molar ratio (isocyanate groups in the polyisocyanate to hydroxyl groups in the polyol) is 1.0 to 2.0. A mixing ratio within this range is preferred because it readily suppresses the residue of unreacted components.

[0162] Alkali metals and alkaline earth metals

[0163] The sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g.

[0164] In this disclosure, alkali metals refer to, for example, lithium, sodium, potassium, rubidium, cesium, or francium. Furthermore, alkaline earth metals refer to, for example, magnesium, calcium, strontium, barium, or radium.

[0165] The sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer is preferably 0.5 × 10⁻⁶. -6 Below mol / g, and more preferably 0.3 × 10⁻⁶. -6 Below mol / g. Although there is no specific limit, this lower limit is, for example, 0.1 × 10⁻⁶. -7 Above mol / g.

[0166] The sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer is preferably 0.1 × 10⁻⁶. -7 ~1.0×10-6 mol / g, preferably 0.1×10 -7 ~0.5×10 -6 mol / g, more preferably 0.1×10 mol / g -7 ~0.3×10 -6 mol / g.

[0167] As mentioned above, alkali metals and alkaline earth metals may inhibit the formation of hydrogen bonds between polymer chains of polyurethane by coordinating with the ether bonds present in polyurethane.

[0168] By making the sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer 0.5 × 10⁻⁶ -6 Below mol / g, it does not inhibit the formation of hydrogen bonds between polyurethane polymer chains and can limit the migration of anions in polyurethane. As a result, the increase in resistivity can be suppressed even during long-term operation.

[0169] The content of alkali metals and alkaline earth metals in the conductive elastic layer is reduced by removing impurities from the manufacturing process of ionic compounds. The amount of anions in the conductive elastic layer increases proportionally to the amount of ionic compounds incorporated in the polyurethane raw material mixture. In other words, by increasing the amount of ionic compounds relative to the polyurethane raw material mixture while removing impurities, the content of alkali metals and alkaline earth metals can be controlled within the aforementioned range.

[0170] The reasons why alkali metals and alkaline earth metals are mixed into the conductive elastic layer include: the fact that such metals were originally included as impurities in the raw materials of the conductive elastic layer (such as ionic compounds, polyols, isocyanates, etc.); and the fact that such metals were mixed in during the manufacturing process of forming the conductive layer, etc.

[0171] For example, it is preferable to use the method for removing metals contained in the ionic compound as a way to control the sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer within the aforementioned range. For example, the metals in the ionic compound can be removed by obtaining the ionic compound through a neutralization reaction described later. Alternatively, the metals in the ionic compound can be removed to a certain extent by passing the ionic compound through an ion exchange membrane multiple times.

[0172] The content of alkali metals and alkaline earth metals in the ionic compound is preferably 30,000 ppm or less, more preferably 15,000 ppm or less, and even more preferably 10,000 ppm or less.

[0173] Since the metals contained in other materials are not included in the ionic compound obtained through neutralization, the amount of alkali metals and alkaline earth metals contained as impurities can be reduced, for example. On the other hand, the yield may be lower when the ionic compound is obtained through neutralization, for the reasons described below.

[0174] According to the research conducted by the inventors, by subjecting a compound having the aforementioned hydroxyalkyl cation precursor and hydroxide ion to a compound having anion and hydrogen ion in a low-concentration, long-term neutralization reaction, ionic compounds with low contents of alkali metals and alkaline earth metals can be obtained in high yield.

[0175] The solution containing the precursor with a hydroxyalkyl cationic structure and the hydroxide ion is strongly basic. In a strongly basic solution, the desorption of the hydroxyalkyl group bonded to the nitrogen atom and the dehydration condensation with another hydroxyalkyl group in the precursor's structure may occur, leading to low yields. It is known that in the case where a hydrogen atom is bonded to the second position of the nitrogen-containing heterocycle in the precursor, particularly in a strongly basic system, an N-heterocyclic carbene structure may be present, and this carbene structure does not participate in the neutralization reaction to obtain the target compound, thus potentially resulting in lower yields.

[0176] Therefore, from a yield point of view, it is considered difficult to use neutralization reaction as a synthetic method for obtaining the above-mentioned precursor salts of hydroxyalkyl cations in some cases.

[0177] On the other hand, the inventors have discovered that the precursor salts of the hydroxyalkyl-containing cations described above can be obtained in high yield by carrying out the neutralization reaction at a low concentration for a long time.

[0178] Methods for manufacturing ionic compounds

[0179] Methods for manufacturing ionic compounds include, for example, the following steps.

[0180] Step (1): The step of obtaining cationic salt intermediate 1, wherein cationic salt intermediate 1 is a cation in an ionic compound represented by the following formulas (A) to (C).

[0181] Step (2): The step of obtaining cationic salt intermediate 2 with hydroxide anions by adding ion exchange resin to cationic salt intermediate 1 and performing ion exchange.

[0182] Step (3): The step of neutralizing the cationic salt intermediate 2 with a compound having the desired anion and hydrogen ion.

[0183] There are no particular limitations on the method used to obtain the cationic salt intermediate 1 in the above step (1), and known methods can be used.

[0184] In step (2) above, the cation salt intermediate 1 is dissolved in water or the like, and an ion exchange reaction is carried out by adding an ion exchange resin, thereby obtaining the cation salt intermediate 2 having hydroxide anions. A known anion exchange resin can be used as the ion exchange resin. After the reaction, the ion exchange resin is filtered to obtain an aqueous solution of the cation salt intermediate 2.

[0185] In step (3) above, the cationic salt intermediate 2 undergoes a neutralization reaction with a compound having the desired anion and hydrogen ion. For example, preferably, an aqueous solution of the anion is added dropwise to the aqueous solution of the cationic salt intermediate 2. As the desired anion, at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion can be used.

[0186] For example, preferably, the aqueous solution of the above-mentioned anion is added dropwise to the aqueous solution of the cationic salt intermediate 2. In this case, the concentration of the aqueous solution of the cationic salt intermediate 2 is preferably 0.1 to 10% by mass. The concentration of the aqueous solution of the anion is preferably 1 to 30% by mass. It is also preferred that the neutralization reaction be carried out for 30 minutes to 10 hours.

[0187] In order to ensure that the sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer falls within the above-mentioned range, the following liquid composition preferably includes ionic compounds.

[0188] The liquid composition preferably comprises at least one of an ionic compound represented by the following structural formula (6) and an ionic compound represented by the following structural formula (7). More preferably, the liquid composition comprises an ionic compound represented by the following structural formula (7).

[0189]

[0190] In structural formula (6), R6 to R8 each independently represent an alkyl group having 1 or more but 4 or fewer carbon atoms, a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms, or a hydrogen atom. At least one of R6 to R8 is a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms. X - It represents anion.

[0191] Preferably, at least one of R6 to R8 is a hydroxyalkyl group having 1 or more but 2 or fewer carbon atoms, while the other two are alkyl groups having 1 or more but 2 or fewer carbon atoms. Preferably, R6 is a hydroxyalkyl group having 1 or more but 2 or fewer carbon atoms, while R7 and R8 are alkyl groups having 1 or more but 2 or fewer carbon atoms. - Preferably, it is a bis(fluorosulfonyl)imide anion.

[0192]

[0193] In structural formula (7), R9 and R10 each independently represent an alkyl group having 1 or more but 4 or fewer carbon atoms, a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms, or a hydrogen atom. At least one of R9 and R10 is a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms. X - It represents anion.

[0194] Preferably, at least one of R9 and R10 is a hydroxyalkyl group having 1 or more but less than 2 carbon atoms. Preferably, R9 and R10 are hydroxyalkyl groups having 1 or more but less than 2 carbon atoms. - The preferred option is the bis(fluorosulfonyl)imide anion.

[0195] The content of the above-mentioned ionic compound in the liquid composition is preferably 95-100% by mass. More preferably, the content of the above-mentioned ionic compound in the liquid composition is 97-100% by mass, and even more preferably 98-100% by mass.

[0196] The sum of the contents of alkali metals and alkaline earth metals in the liquid composition is preferably less than 30,000 ppm.

[0197] The sum of the contents of alkali metals and alkaline earth metals in the liquid composition is preferably 15,000 ppm or less, and more preferably 10,000 ppm or less. Although no particular lower limit is specified, it is, for example, 100 ppm or more. The sum of the contents of alkali metals and alkaline earth metals in the liquid composition is preferably 100 to 30,000 ppm, more preferably 100 to 15,000 ppm, and even more preferably 100 to 10,000 ppm.

[0198] The viscosity of the liquid composition at 23°C is preferably 1 to 1000 mPa·s. A viscosity less than 1 mPa·s at 23°C may increase the mixing time required to enhance the dispersibility of the liquid composition in the elastic layer forming material described later. If the viscosity is greater than 1000 mPa·s, it may be difficult to uniformly disperse the liquid composition in the elastic layer forming material described later.

[0199] By bringing the viscosity of the liquid composition at 23°C into the aforementioned range, it becomes easier to uniformly control the dispersibility of the liquid composition in the elastic layer forming material described later, and further demonstrates the effects of this disclosure.

[0200] The viscosity of a liquid composition at 23°C can be controlled, for example, by the type and amount of ionic compounds. For instance, by setting the content of ionic compounds in the liquid composition within the aforementioned range, it becomes easier to control the viscosity within that range.

[0201] The viscosity of the liquid composition at 23°C is preferably 1 to 100 mPa·s, more preferably 3 to 50 mPa·s, and even more preferably 5 to 20 mPa·s.

[0202] By using the above-described liquid composition as an ionic compound to form a conductive elastic layer, it becomes easier to control the sum of the alkali metal and alkaline earth metal contents in the conductive elastic layer to be 1.0 × 10⁻⁶. -6 The concentration is below mol / g, further limiting the migration of anions in the polyurethane. In this way, it becomes easier to properly manufacture conductive elastic rollers that can suppress the increase in resistance even during prolonged operation.

[0203] The difference between the solubility parameter of polyurethane and the solubility parameter of anion is preferably 0.60~2.00 (J / cm). 3 ) 0.5 .

[0204] By ensuring that the difference in solubility parameters between polyurethane and anion is 0.60 (J / cm²). 3 ) 0.5 Under the above conditions, the difference between the solubility parameters becomes sufficiently large, and therefore it becomes easier to limit the migration of anions in polyurethane. This is achieved by ensuring that the difference in solubility parameters meets a value of 2.00 (J / cm²). 3 ) 0.5 The following conditions facilitate the moderate movement of anions within polyurethane. By setting the difference in solubility parameters between polyurethane and anions within the aforementioned range, it becomes easier to control the resistance value while maintaining the conductivity of the conductive elastic roller.

[0205] Although there are no particular limitations on the solubility parameters of polyurethane, the preferred solubility parameters are 3.00~15.00 (J / cm). 3 ) 0.5 More preferably, it is 5.00~10.00 (J / cm). 3 ) 0.5 More preferably, it is 7.00~9.00 (J / cm). 3 ) 0.5 .

[0206] Although there are no particular restrictions on the solubility parameters of anions, the preferred solubility parameters are 5.00~15.00 (J / cm³). 3 ) 0.5 More preferably, it is 7.00~13.00 (J / cm). 3 ) 0.5 More preferably, it is 9.00~10.00 (J / cm). 3 ) 0.5 .

[0207] Note that the method for measuring the solubility parameter will be described later.

[0208] When the conductive elastic layer of the conductive elastic roller is measured by a differential scanning calorimeter (DSC), it is preferable that when the temperature is increased from 30°C to 200°C at a heating rate of 10°C / min, there is more than one endothermic peak in the specific heat curve in the range of 40°C to 70°C.

[0209] The inventors believe that the stability of a conductive elastic layer can be confirmed by observing that the layer exhibits more than one endothermic peak in the high-temperature range during DSC measurements, based on its thermal responsiveness.

[0210] When the conductive elastic layer includes the aforementioned anionic structure and the aforementioned cationic structure of polyurethane, a pseudo-crosslinking structure is formed in the polyurethane due to the electrical interaction between the anionic and cationic structures. The presence of such pseudo-crosslinking structures can be detected as an endothermic peak by DSC measurement of the conductive elastic layer.

[0211] The presence of more than one endothermic peak in the high-temperature range of 40℃ to 70℃ is considered to indicate that strong pseudo-crosslinking has been formed in the polyurethane. Therefore, it becomes easier to restrict anion migration and further suppress the increase in resistivity.

[0212] The conductive elastic layer has one or more endothermic peaks, more preferably in the temperature range of 50°C to 70°C, and even more preferably in the temperature range of 60°C to 70°C. Examples of ways to increase the endothermic peak temperature include reducing the content of alkali metals and alkaline earth metals in the conductive elastic layer and selecting materials to reduce the distance between polyurethane crosslinking points, etc. For example, the endothermic peak temperature can be increased by selecting low molecular weight materials used to form the polyurethane.

[0213] As described above, in particular, a conductive elastic roller including a conductive elastic layer can be suitably used as a toner supply roller. The toner supply roller is required to have the ability to uniformly supply toner to the surface of the developing roller, and characteristics such as the average cell diameter on the surface, the number of cells and the airflow rate, as well as the density of the entire foamed conductive elastic layer, are important.

[0214] The conductive elastic roller is preferably a foamed conductive elastic roller. In other words, the conductive elastic layer is preferably a foamed conductive elastic layer.

[0215] The foamed conductive elastic layer contains numerous significant microstructures. These microstructures effectively hinder the migration of anions. Therefore, because the conductive elastic layer is a foamed conductive elastic layer, the migration of anions can also be limited by the structure of the conductive elastic layer, maintaining its low resistance value even for a longer period of time.

[0216] Although there are no particular limitations on the physical properties of the foamed conductive elastic layer, it is preferred, for example, to have values ​​within the following range.

[0217] The average pore diameter of the foamed conductive elastic layer is preferably 80 to 500 μm. By ensuring that the average pore diameter of the foamed conductive elastic layer falls within this range, the migration of anions can be more appropriately restricted, and thus the low resistance characteristic can be maintained for an even longer period of time.

[0218] The average pore diameter of the foamed conductive elastic layer is more preferably 100~500μm, and even more preferably 200~400μm.

[0219] The average cell diameter on the surface can be controlled, for example, by the production conditions of the conductive elastic layer and the addition of the additives described later. For example, the average cell diameter on the surface can be controlled within the above range by the type and amount of foaming agent, the type and amount of foaming stabilizer, etc., which will be described later.

[0220] The number of cells on the surface of the foamed conductive elastic layer is preferably 50 cells / inch or more and 300 cells / inch or less. The airflow rate on the surface of the foamed conductive elastic layer is preferably 0.5 L / min or more and 3.0 L / min or less. The density of the foamed conductive elastic layer is preferably, for example, 0.05 g / cm³. 3 Above and 0.20 g / cm 3 the following.

[0221] other

[0222] Catalysts, foaming agents, foaming stabilizers and other additives may be used in the conductive elastic layer of the conductive elastic roller as needed.

[0223] There are no particular limitations on the catalyst, and it can be appropriately selected and used from a variety of conventionally known catalysts. For example, amine catalysts (triethylenediamine, bis(dimethylaminoethyl) ether, N,N,N′,N′-tetramethylhexanediamine, 1,8-diazabicyclo(5,4,0)undecene-7,1,5-diazabicyclo(4,3,0)nonane-5,1,2-dimethylimidazolium, N-ethylmorpholine, or N-methylmorpholine, etc.), organometallic catalysts (tin octoate, tin oleate, dibutyltin dilaurate, dibutyltin diacetate, tetraisopropoxytitanium, tetra-n-butoxytitanium, and tetra(2-ethylhexyloxy)titanium, etc.), and acid salt catalysts (carboxylates, formates, octanoates, and borates, etc.) obtained by reducing the initial activity of amine and organometallic catalysts can be used. One catalyst or a combination of two or more catalysts can be used.

[0224] There are no particular limitations on the foaming agent, and it is appropriate to select and use a variety of known foaming agents. In particular, water reacts with polyisocyanates to produce carbon dioxide gas, and is therefore appropriately used as a foaming agent. Furthermore, other foaming agents can also be used with water.

[0225] There are no particular limitations on foaming stabilizers, and a variety of known foaming stabilizers can be appropriately selected and used. For example, silicone foaming stabilizers can be used.

[0226] Other additives, such as crosslinking agents, flame retardants, colorants, ultraviolet absorbers, antioxidants, or conductive fillers, may be used as needed to the extent that the effects of this disclosure are not impaired. Carbon black, as well as conductive metals such as aluminum and copper, may be used as conductive fillers. Furthermore, other ionic compounds may also be used in combination to the extent that the effects of this disclosure are not compromised.

[0227] When forming a conductive elastic layer, from a stability point of view, the content of ionic compounds in the raw material mixture is preferably 0.1 to 30 parts by mass relative to 100 parts by mass of the adhesive resin forming the conductive elastic layer. When multiple ionic compounds are used together, the sum of their contents preferably falls within the above range.

[0228] Method for forming foamed conductive elastic layer

[0229] There are no particular limitations on the method of forming the conductive elastic layer when it is a foamed conductive elastic layer, and known methods can be used. Any method can be used, such as using a foaming agent or mixing air bubbles by mechanical stirring. The foaming ratio can be appropriately determined and is not particularly limited.

[0230] For example, the foamed conductive elastic layer of the foamed conductive elastic roller is obtained by causing a reaction in the elastic layer forming material obtained by mixing the following materials, while simultaneously foaming the material.

[0231] 1. Materials used to form adhesive resins

[0232] - Polyols (e.g., polyether polyols)

[0233] - Polyisocyanates

[0234] 2. Compounds whose cationic structure has at least one functional group including a hydroxyl, amino, or glycidyl group.

[0235] 3. Catalyst

[0236] 4. Foaming stabilizer

[0237] 5. Foaming agent

[0238] The elastic layer forming material comprises a compound containing a nitrogen-containing heteroaromatic ring structure and a mixture of polyurethane raw materials for forming polyurethane. As the compound containing the nitrogen-containing heteroaromatic ring structure, the aforementioned ionic compound or a liquid composition containing an ionic compound can be used. The polyurethane raw material mixture includes, for example, polyols and polyisocyanates.

[0239] The elastic layer forming material preferably comprises at least a liquid composition containing an ionic compound, a polyol, and a polyisocyanate. When the elastic layer is formed as a foam, it may further contain a foaming agent.

[0240] The ionic compound is preferably any ionic compound represented by formulas (A) to (C) below. The ionic compound is preferably obtained by the above-described neutralization reaction. The ionic compound is more preferably an ionic compound represented by the above structural formula (6).

[0241]

[0242] In formula (A), R11 and R12 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 5-membered ring together with the nitrogen atoms bonded to each of R11 and R12. R13 to R15 represent functional groups including hydroxyl, amino, or glycidyl groups, hydrogen atoms, or hydrocarbon groups having 1 or more but 4 or fewer carbon atoms, and at least one of R13 and R15 represents a functional group including hydroxyl, amino, or glycidyl groups. At least one of R13 to R15 is preferably a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms. - It represents anion.

[0243]

[0244] In formula (B), R16 and R17 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 6-membered ring together with each of the nitrogen atoms bonded to R16 and R17. R18 and R19 represent functional groups including hydroxyl, amino, or glycidyl groups, hydrogen atoms, or hydrocarbon groups having 1 or more but 4 or fewer carbon atoms, and at least one of R18 and R19 represents a functional group including hydroxyl, amino, or glycidyl groups. At least one of R18 and R19 is preferably a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms. - It represents anion.

[0245]

[0246] In formula (C), R20 represents the hydrocarbon group required to form a nitrogen-containing heteroaromatic ring together with the nitrogen atom bonded to R20. R21 and R22 represent functional groups including hydroxyl, amino, or glycidyl groups, hydrogen atoms, or hydrocarbon groups having 1 or more but 4 or fewer carbon atoms, and at least one of R21 and R22 represents a functional group including hydroxyl, amino, or glycidyl groups. At least one of R21 and R22 is preferably a hydroxyalkyl group having 1 or more but 4 or fewer carbon atoms. X - It represents anion.

[0247] Note that, from the viewpoint of conductivity and suppressing resistance changes caused by current flow, the sum of the contents of ionic compounds in the elastic layer forming material is preferably within the following range. In other words, the content of ionic compounds in the elastic layer forming material is preferably 0.1 to 30 parts by weight relative to 100 parts by weight of adhesive resin, more preferably 1.0 to 10.0 parts by weight, and even more preferably 3.0 to 5.0 parts by weight.

[0248] Although there is no particular limitation on the content of polyols in the elastic layer forming material, the content of polyols is preferably 50.0 to 90.0 parts by mass, more preferably 60.0 to 85.0 parts by mass, and even more preferably 70.0 to 80.0 parts by mass.

[0249] Although there is no particular limitation on the content of polyisocyanate in the elastic layer forming material, the content of polyisocyanate is preferably 5.0 to 30.0 parts by weight, more preferably 7.0 to 25.0 parts by weight, and even more preferably 10.0 to 20.0 parts by weight.

[0250] Although there is no particular limitation on the content of foaming agent in the elastic layer forming material, the content of foaming agent is preferably 0.3 to 3.0 parts by weight, more preferably 0.5 to 2.5 parts by weight, and even more preferably 0.7 to 2.0 parts by weight.

[0251] A conductive elastic layer can be formed by mixing materials to induce a reaction. There are no particular limitations on the mixing temperature and time. The mixing temperature is typically in the range of 10–90°C, and preferably in the range of 20–70°C. Furthermore, the mixing time is typically in the range of 1 second to 15 minutes, and preferably in the range of 3 seconds to 10 minutes, depending on the structure of the mixing unit used or the rotation conditions, etc.

[0252] There are no particular limitations on the bonding method between the substrate and the conductive elastic layer. Methods such as: pre-placing the substrate in a mold (forming mold) and casting and curing the aforementioned raw material mixture; or pre-forming the raw material mixture into a predetermined shape to form a conductive elastic layer, and then bonding it to the substrate; and so on. In any method, an adhesive layer may be provided between the substrate and the conductive elastic layer as needed. Known materials such as adhesives or hot melt sheets can be used as this adhesive layer.

[0253] In the case of a mixture of casting and curing raw materials, a release agent can be pre-applied to the inner wall of the mold. Known release agents can be used as the release agent. Examples include aqueous release agents containing wax components and silicone oil, and release agents obtained by dissolving fluoropolymers in fluorinated solvents. An example of a fluoropolymer release agent is a fluoropolymer release agent (trade name: FLUORO SURF FG-5093F130-0.5, manufactured by Fluoro Technology Co. Ltd.).

[0254] There are no particular limitations on the method for forming the conductive elastic layer. For example, in addition to the method described above, which involves casting a mixture of raw materials into a mold having a predetermined shape, the following methods can also be used. Examples of such methods include methods for cutting block polyurethane foam into predetermined sizes by cutting; methods for obtaining predetermined sizes by grinding; and methods achieved by appropriately combining these methods.

[0255] The manufacturing method of the conductive elastic roller preferably includes, for example, a step of injecting an elastic layer forming material into a mold having a substrate disposed therein, and a step of heating the mold and curing the elastic layer forming material, thereby forming a conductive elastic layer.

[0256] The conductive elastic roller may include a conductive elastic layer that is not a foam.

[0257] The conductive elastic roller preferably comprises a conductive substrate, an elastic layer on the substrate, and a surface layer on the elastic layer. The surface layer preferably comprises the aforementioned polyurethane and the aforementioned anionic polymer. When a surface layer is formed, the elastic layer and the surface layer function as a conductive elastic layer.

[0258] The following will describe an example of a method for manufacturing a conductive elastic roller in which the elastic layer is not foamed.

[0259] The manufacturing method of such conductive elastic rollers includes, for example, a step of forming an elastic layer on the outer peripheral surface of a substrate and a step of forming a surface layer on the outer surface of the elastic layer, thereby obtaining a conductive elastic roller.

[0260] The aforementioned substrate can be used as the substrate. The elastic layer is preferably, for example, a silicone rubber elastic layer.

[0261] As a material for forming the elastic layer of silicone rubber, a silicone rubber composition containing liquid silicone rubber material and additives such as heat resistance improvers and catalysts as needed can be used.

[0262] For example, a silicone rubber composition is injected as an elastic layer material into a mold in which a substrate is disposed, and the silicone rubber is cured. For example, a silicone rubber elastic layer can be formed on the outer surface of the substrate by heating at a temperature of 100°C to 200°C for 5 to 20 minutes.

[0263] A surface layer is formed on the outer surface of the elastic layer thus formed. As the material for forming the surface layer, a coating for forming the surface layer can be used, comprising a compound containing a nitrogen-containing heteroaromatic ring structure and a mixture of polyurethane raw materials forming polyurethane. As the compound containing the nitrogen-containing heteroaromatic ring structure, the above-described liquid composition can be used. The polyurethane raw material mixture includes, for example, polyols and polyisocyanates.

[0264] A surface layer forming coating is applied to the surface of the formed elastic layer. For example, after forming the elastic layer, a coating film is formed on the surface of the elastic layer by forming the elastic layer and immersing it in a pre-prepared surface layer forming coating. The coating film is then dried, followed by heat treatment, thereby forming a polyurethane-containing surface layer. The heating is preferably carried out, for example, at 100°C to 200°C for 30 minutes to 3 hours.

[0265] A conductive elastic roller comprising a substrate, an elastic layer on the substrate, and a surface layer on the elastic layer can be obtained through the above process.

[0266] Electrophotographic image forming equipment

[0267] An electrophotographic image forming apparatus according to another aspect of this disclosure includes the aforementioned conductive elastic roller. In other words, the conductive elastic roller according to one aspect of this disclosure can be used as a developing roller, a charging roller, and a toner supply roller in an electrophotographic image forming apparatus. When the conductive elastic roller is a foamed conductive elastic roller, it is particularly suitable for use as a developer supply roller.

[0268] Foamed conductive elastic rollers can also be used in any developing apparatus in non-contact or contact developing apparatus that uses magnetic single-component toners or non-magnetic single-component toners.

[0269] An electrophotographic image forming apparatus includes at least: an electrophotographic photosensitive element; a developing roller disposed in contact with the electrophotographic photosensitive element; and a developing roller for supplying developing agent to the developing roller. Preferably, the developing roller is the aforementioned foamed conductive elastic roller.

[0270] Figure 2This is a schematic cross-sectional view showing an example of an electrophotographic image forming apparatus in which a foamed conductive elastic roller is installed as a toner (developer) supply roller in a contact developing apparatus using a single-component toner.

[0271] The developing apparatus 22 includes a toner container 20 containing toner 15 as a single-component toner; a developing roller 16; a toner supply roller 19 supplying toner to the developing roller 16; and a developing blade 21 for adjusting the thickness of the toner layer on the developing roller 16. The developing roller 16 is located in an opening extending longitudinally within the toner container 20 and is mounted in contact with the electrophotographic photosensitive element 18.

[0272] Note that the electrophotographic photosensitive element 18, the cleaning blade 26, the waste toner storage container 25, and the charging roller 24 can be installed in the main body of the electrophotographic image forming apparatus. A developing apparatus 22 is provided for preparing various color toners for black (Bk), cyan (C), magenta (M), and yellow (Y), and color printing is possible.

[0273] The printing operation of the electrophotographic image forming device will be described below.

[0274] The electrophotographic photosensitive element 18 rotates in the direction of the arrow and is uniformly charged by the charging roller 24, thereby charging the electrophotographic photosensitive element 18. Next, an electrostatic latent image is formed on the surface of the electrophotographic photosensitive element 18 using laser light 23 (which is an exposure means). The electrostatic latent image is visualized (developed) into a toner image by the developing apparatus 22 using toner 15 applied by the developing roller 16, which is in contact with the electrophotographic photosensitive element 18. This development is a so-called reverse development, in which the toner image is formed in the exposure section.

[0275] The toner image formed on the electrophotographic photosensitive element 18 is transferred onto paper 34 (the recording medium) using a transfer roller 29 (which is the transfer element). The paper 34 is fed into the equipment via a feed roller 35 and an adsorption roller 36, and is transported between the electrophotographic photosensitive element 18 and the transfer roller 29 using an annular transfer conveyor belt 32. The transfer conveyor belt 32 is operated by a driven roller 33, a drive roller 28, and a tension roller 31. Voltage is applied from a bias power supply 30 to the developing roller 16, the developing blade 21, the toner supply roller 19, and the adsorption roller 36.

[0276] The paper 34, on which the toner image has been transferred, is fixed using the fixing device 27 and then ejected from the device, completing the printing operation. Simultaneously, any residual toner remaining on the electrophotographic photosensitive element 18 that has not been transferred is scraped off using the cleaning blade 26 (a cleaning component for cleaning the surface of the photosensitive element) and stored in the waste toner storage container 25. The above printing operation is repeated on the cleaned electrophotographic photosensitive element 18.

[0277] Processing box

[0278] According to another aspect of this disclosure, the processing cartridge includes the aforementioned conductive elastic roller. In particular, the conductive elastic roller can be suitably used as the toner supply roller 19 in the processing cartridge.

[0279] Figure 3 This is a schematic cross-sectional view showing an example of a processing cartridge. The processing cartridge 17 is configured to be detachably mounted to the main body of an electrophotographic image forming apparatus. Furthermore, the processing cartridge 17 integrates a developing unit 22, an electrophotographic photosensitive element 18, a cleaning blade 26 as a cleaning means, a waste toner storage container 25, and a charging roller 24 as a charging means.

[0280] Here, the developing apparatus 22 includes a developing roller 16 and a developing blade 21 as a developing means. The developing apparatus 22 also includes a toner container 20, and the toner container 20 is filled with toner 15. The toner 15 in the toner container 20 is supplied to the surface of the developing roller 16 through a toner supply roller 19, and a layer of toner 15 having a predetermined thickness is formed on the surface of the developing roller 16 by the developing blade 21.

[0281] Method for supplying toner via a toner supply roller

[0282] Examples of methods for supplying toner to the developing roller 16 via the toner supply roller 19 include mechanical supply methods and electrical supply methods.

[0283] The mechanical supply method involves supplying toner by holding it on the surface layer of the toner supply roller 19 and through contact with the developing roller 16. In this case, if the surface layer of the toner supply roller 19 is a porous layer, such as a foamed layer, the amount of toner held increases, and the toner can be supplied more efficiently. Furthermore, if the surface layer of the toner supply roller 19 is a conductive elastic layer, the held toner is pushed out by the contraction of the conductive elastic layer upon contact with the developing roller 16, thus facilitating the discharge of toner from the toner supply roller 19.

[0284] The electrical supply method utilizes the bias force of the charged toner, which is generated by the bias voltage difference between the bias voltage applied to the toner supply roller 19 and the bias voltage applied to the developing roller 16. Specifically, when the polarity of the bias voltage difference is the same as the normal charged polarity of the toner, the bias force from the toner supply roller 19 on the developing roller 16 side acts on the toner at the contact portion. The toner is supplied in this manner.

[0285] The processing cartridge preferably has a contact member that is electrically connected to an electrical contact point of the body when the processing cartridge is mounted onto the body of the electrophotographic image forming apparatus. The processing cartridge includes a developing roller and a developer supply roller for supplying toner to the developing roller, and is preferably configured to apply a voltage between the developing roller and the developer supply roller via an electrical connection to the body. The developer supply roller is preferably the aforementioned conductive elastic roller.

[0286] The measurement method for describing the physical properties of conductive elastic rollers will be described.

[0287] Measurement of solubility parameter (SP value)

[0288] The solubility parameters (SP values) of polyurethane and anionic polyurethane were measured as follows.

[0289] Sample preparation

[0290] When the raw material for the polyurethane used in the conductive elastic roller is available, measurements are performed using samples obtained by synthesizing polyurethane alone. Alternatively, samples obtained by acquiring and synthesizing the raw material based on information obtained from structural analysis of the polyurethane used in the conductive elastic roller can also be used.

[0291] In the case of measuring anions, the anionic component can be extracted from the conductive elastic roller and used as a sample. For example, 2g of conductive elastic layer can be immersed in 10ml of acetone to extract anions. The solution obtained by evaporating the acetone to dryness and then dissolving it in 10ml of acetonitrile can be used as a sample.

[0292] In addition, anionic components can be specified through analysis, and similar anions obtained separately can be used as samples.

[0293] Measurement of SP value

[0294] Weigh 0.5g of the above sample into a 100ml beaker, and add 10ml of good solvent using a pipette. Stir thoroughly to dissolve the mixture. Next, add a poor solvent using a 50ml burette and measure the amount added at the point where turbidity appears.

[0295] In this disclosure, acetone is used as a good solvent and n-hexane as a poor solvent when measuring polyurethane. When measuring anions, 1,4-dioxane is used as a good solvent and deionized water is used as a poor solvent.

[0296] The SP value δ is calculated as follows. Measurements are performed three times, and the arithmetic mean is defined as the SP value.

[0297]

[0298] Vi: Molar volume of solvent (ml / mol)

[0299] φi: Volume fraction of each solvent at the point where turbidity appears.

[0300] δi: SP value of each solvent

[0301] ml: Low SP poor solvent mixing system

[0302] mh: High SP poor solvent mixture system

[0303] The molar volumes and SP values ​​of solvents 1 and 2 (good solvent and bad solvent) can be obtained using the following formula.

[0304] Vm=V1V2 / (φ1V2+φ2V1)

[0305] δm=φ1δ1+φ2δ2

[0306] Reference: "JPS A-1, 5, 1671~1681 (1967), SUH CLARKE"

[0307] Methods for evaluating the content and viscosity of liquid compositions

[0308] The content of ionic compounds in a liquid composition can be determined by methods based on thermogravimetric loss and proton nuclear magnetic resonance (NMR). 1 The measurement is performed by measuring the solids content ratio using methods such as 1H-NMR or liquid chromatography-mass spectrometry (LC / MS). Measurements can be performed using one or more of these methods. Specifically, for example, the measurement can be performed using the methods described below.

[0309] 10 mg of the liquid composition was dissolved in 2 mL of acetonitrile to prepare a 5000 μg / mL solution. 960 μL of acetonitrile (25-fold dilution) was added to 40 μL of this adjusted solution to prepare a 1.0 mL 200 μg / mL solution. The mixture was then filtered through a 0.2 μm filter to obtain the measurement sample.

[0310] The following equipment and conditions were used as measurement criteria.

[0311] equipment

[0312] -Ultimate 3000 / LCQ FLEET (manufactured by Thermo)

[0313] (HPLC conditions)

[0314] -Column: Acclaim Trinity P1 3μm 2.1×100mm (manufactured by Thermo)

[0315] (A mixed mode of reversed-phase (RP), strong cation exchange (SCX), and weak anion exchange (WAX))

[0316] - Column temperature: 30℃

[0317] -Mobile phase: A: Acetonitrile; B: 100mM ammonium formate aqueous solution (pH 5.0); C: Pure water

[0318] A / B / C = 70 / 1 / 29 (equivalence)

[0319] - Flow rate: 0.5 mL / min

[0320] - Detector: Corona Veo (Corona CAD), PDA (190nm~800nm)

[0321] -Injection volume: 10μL

[0322] -Analysis time: 10 minutes

[0323] Mass spectrometry analysis

[0324] -Ionization: ESI positive / negative

[0325] - Scan range: M / z 50~2000

[0326] Establishment of calibration curves

[0327] A standard curve was established using a calibration curve preparation sample prepared by pre-mixing ionic compounds at mass concentrations of 25%, 50%, and 75% in 1 g of ion-exchanged water, and the results of measurements of the ionic compounds before mixing with ion-exchanged water under the aforementioned analytical conditions.

[0328] analyze

[0329] Calculate the peak area corresponding to the mass of the ionic compound. The results of sample measurements and calibration curves are used to determine the content of the ionic compound in the liquid composition.

[0330] The content of alkali metals and alkaline earth metals in a liquid composition can be measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) or inductively coupled plasma mass spectrometry (ICP-MS). Specifically, it can be measured, for example, by the following methods.

[0331] Weigh 10 mg of the liquid composition, add 5 mL of ultrapure water, and filter the mixture using a 0.45 μm membrane filter to obtain the measurement sample.

[0332] Analysis conditions

[0333] - Equipment: Integrion RFIC (manufactured by Thermo)

[0334] -Standard Solution: Cation Mixed Standard Solution-II (Manufactured by Kanto Chemical Co., Inc.)

[0335] - Column: CS-16 (manufactured by Thermo)

[0336] - Column temperature: / 40℃

[0337] -Mobile phase: 30mM aqueous solution of methanesulfonic acid (cationic)

[0338] - Flow rate: 0.36 mL / min (cationic)

[0339] - Detector: - Conductivity

[0340] -Injection volume: 10μL

[0341] -Analysis time: 27 minutes (cations)

[0342] Establishment of calibration curves

[0343] The above standard solutions were mixed with ion-exchanged water, and samples with concentrations of 10% and 50% by mass, as well as the samples before mixing with ion-exchanged water, were used as samples for calibration curve preparation. These samples were analyzed to establish the calibration curve.

[0344] analyze

[0345] The peak area of ​​the measured sample was calculated for each cation. The results of the measured samples, along with the calibration curve, were used to determine the content of alkali metals and alkaline earth metals in the liquid composition.

[0346] In addition, the viscosity of a liquid composition at 23°C can be measured using a type B viscometer, type E viscometer, or rheometer. Specifically, the measurement can be performed, for example, by the following methods.

[0347] An E-type viscometer (RE500L, manufactured by Toki Sangyo Co., Ltd.) with a 0.8° × R24 conical rotor was used. The viscosity of the liquid composition was measured at a measurement temperature of 23°C using a sample volume of 0.6 ml.

[0348] Evaluation method for the sum of alkali metal and alkaline earth metal contents in conductive elastic layers

[0349] The sum of the contents of alkali metals and alkaline earth metals in the conductive elastic layer is measured as follows.

[0350] To extract alkali and alkaline earth metals, 0.5 g of the conductive elastic layer was immersed in 5 ml of acetone, followed by evaporation of the acetone to dryness. The extract dissolved in 5 ml of ultrapure water was used as the sample.

[0351] Ionic compounds or liquid compositions containing ionic compounds can also be used as samples. When using ionic compounds as samples, samples can be obtained similarly to those described above, except that 0.01 g of the ionic compound is immersed in 10 ml of acetone.

[0352] The samples were measured by ion chromatography, and the contents of alkali metals and alkaline earth metals were calculated from the spectral quantities of alkali metals and alkaline earth metals.

[0353] The measurement conditions for ion chromatography are as follows.

[0354] - Device: Integrion RFiC (manufactured by Thermo)

[0355] -Standard Solution: Multivalent Cation Standard Solution-II (manufactured by Kanto Chemical Co., Ltd.)

[0356] - Column: CS-16 (manufactured by Thermo)

[0357] - Column temperature: 40℃ (cationic)

[0358] Mobile phase: 30mM methanesulfonic acid aqueous solution

[0359] - Flow rate: 0.36 mL / min

[0360] - Detector: Conductivity

[0361] -Injection volume: 10μL

[0362] -Analysis time: 27 minutes

[0363] In addition, the following standard solutions 1 to 3 were prepared as standard samples of various alkali metals and alkaline earth metals, and calibration curves for alkali metals and alkaline earth metals were established by measuring under the above conditions.

[0364] -Standard Solution 1- The above standard solution

[0365] -Standard Solution 2- Dilute the above standard solution with ultrapure water to a concentration of 0.50% by mass.

[0366] -Standard Solution 3- Dilute the above standard solution with ultrapure water to a concentration of 0.20% by mass.

[0367] The contents of alkali metals and alkaline earth metals in the sample were obtained from the established calibration curves.

[0368] The contents of the alkali metals and alkaline earth metals obtained therefrom are divided by their respective elemental amounts and processed into the molar masses of the alkali metals and alkaline earth metals contained in the conductive elastic layer. The sum of the contents of the alkali metals and alkaline earth metals obtained is defined as the sum of the contents of the alkali metals and alkaline earth metals in the conductive elastic layer of this disclosure. The above-mentioned sum of contents is the number of moles of alkali metals and alkaline earth metals per unit mass of conductive elastic layer.

[0369] Measurement of average surface pore diameter

[0370] The method for measuring the average pore diameter on the surface of the conductive elastic layer is as follows.

[0371] Measurements were performed using a laser microscope (the “Shape Measurement Laser Microscope VK-8700” or equivalent analyzer manufactured by Keyence Corporation).

[0372] The measurement areas correspond to three regions at 10%, 50%, and 90% of the total length of the conductive elastic roller, starting from one end in the longitudinal direction. For each measurement area, measurements are taken at four locations at 0°, 90°, 180°, and 270° in the circumferential direction of the conductive elastic roller, for a total of 12 points.

[0373] The observation area is defined as a region of 1.0 mm × 1.4 mm. Twenty cells are selected within each observation area, and the diameter of the largest inscribed circle in the skeleton of each cell is measured. The arithmetic mean of the cell diameters at a total of 12 points is defined as the surface-average cell diameter in this disclosure.

[0374] Differential scanning calorimetry of conductive elastic layers

[0375] Differential scanning calorimetry was performed on the conductive elastic layer using the following method.

[0376] The differential scanning calorimeter (MDSC-2920, manufactured by TA Instruments) is used to perform measurements under the following conditions according to ASTM D3418-82.

[0377] As a measurement sample, a conductive elastic layer was cut from a conductive elastic roller, and 10 mg of it was precisely weighed and placed in an aluminum pan. An empty aluminum pan was used as a reference.

[0378] The measurement temperature range is set to 30℃~200℃, and the temperature is increased from 30℃ to 200℃ at a rate of 10℃ / min.

[0379] On the specific heat curve (i.e., DSC curve) obtained during the heating process, the intersection point of the straight line equidistant from the extended lines of the baselines before and after the specific heat change along the vertical axis and the curve at the step change portion of the glass transition is defined as the glass transition temperature (Tg). Confirm the temperature at which the endothermic peak is observed on the DSC curve.

[0380] Example

[0381] This disclosure will be described in further detail by way of examples, but these examples are not intended to limit the invention in any way.

[0382] An ionic compound that is a raw material for polyurethane contained in the conductive elastic layer of a conductive elastic roller.

[0383] Synthesis of compositions containing ionic compounds

[0384] Composition C-1

[0385] A stirring rod and 60 mL of tetrahydrofuran (THF, manufactured by Kanto Chemical Co., Inc.) were placed in a round-bottom flask equipped with a Dimroth condenser. 24.0 g (0.60 mol) of sodium hydride (60% by mass, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) were dispersed, and the flask was cooled in an ice bath. A solution of 10.2 g (0.15 mol) of imidazole (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 60 mL of THF was slowly added dropwise. The ice bath was then removed, and the mixture was stirred at room temperature for two hours. 47.6 g (0.38 mol) of 2-bromoethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added at room temperature, and the mixture was heated under reflux at 70 °C for seven hours. The reaction mixture was filtered, insoluble fractions were washed with THF, and the solvent in the resulting filtrate was removed by vacuum distillation. The product thus obtained was dissolved in 590.5 g of water, 179.3 g of ion exchange resin DOWEX550A OH (manufactured by DuPont) was added, and the mixture was stirred at room temperature for one hour.

[0386] The ion exchange resin was filtered, and an aqueous solution of 27.2 g of lithium bis(fluorosulfonyl)imide (manufactured by Aaron Chemicals) dissolved in 379.6 g of water was added dropwise to the resulting aqueous solution over two hours. Note that the pH was monitored during the addition, and the addition was stopped at pH 6.3. The solvent in the resulting aqueous solution was removed by vacuum distillation to obtain composition C-1 of Example 1.

[0387] The ionic compound 1 contained in composition C-1 is a compound represented by the following formula (8). The physical properties of composition C-1 are shown in Table 1.

[0388] Ionic compound 1

[0389]

[0390] Compositions C-2, C-3 and C-7

[0391] Except for altering the anionic raw materials and their proportions as described in Table 1, compositions C-2, C-3, and C-7 were obtained similarly to the synthesis of composition C-1. The ionic compounds 2, 3, and 7 contained in compositions C-2, C-3, and C-7 are represented by structural formulas and combinations of anions corresponding to the structures of the ionic compounds described in Table 1. The physical properties of compositions C-2, C-3, and C-7 are shown in Table 1.

[0392] [Table 1]

[0393]

[0394] In the table, "viscosity" refers to the viscosity of the liquid composition at 23°C. Since compositions C-6, C-8, and C-9 are solids, their viscosities were not measured.

[0395] Composition C-4

[0396] 15.0 g of 5-methylpyrazine-2-methanol (manufactured by Sigma-Aldrich CO., LLC) and 9.2 g of sodium hydride (60%, dispersed in liquid paraffin) (manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 80.0 g of tetrahydrofuran. At room temperature, 18.9 g of iodomethane (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in the tetrahydrofuran was added dropwise over 30 minutes, followed by heating at 85°C under reflux for 12 hours.

[0397] Next, 100 ml of water was added to the reaction solution, the reaction solution was filtered, the insoluble fraction was washed away with THF, and the solvent in the resulting filtrate was removed by vacuum distillation. The product thus obtained was dissolved in 590.5 g of water, 179.3 g of ion exchange resin DOWEX 550A OH (manufactured by DuPont) was added, and the mixture was stirred at room temperature for 1 hour.

[0398] The ion exchange resin was filtered, and an aqueous solution obtained by dissolving 27.2 g of lithium bis(fluorosulfonyl)imide (Aaron Chemicals) in 379.6 g of water was added dropwise to the resulting aqueous solution over two hours. Note that the pH was monitored during the addition, and the addition was stopped when the pH reached 6.3. The solvent in the resulting aqueous solution was removed by vacuum distillation to obtain composition C-4. The ionic compound 4 contained in composition C-4 is represented by a combination of structural formulas and anions corresponding to the structures described in Table 1. The physical properties of composition C-4 are shown in Table 1.

[0399] Composition C-5

[0400] Except for changing the anionic raw materials and their proportions as described in Table 1, composition C-5 was obtained in a similar manner to the synthesis of composition C-4.

[0401] The ionic compound 5 contained in composition C-5 is a compound represented by a combination of structural formulas and anions corresponding to the ionic compounds described in Table 1. The physical properties of composition C-5 are shown in Table 1.

[0402] Composition C-6

[0403] 15.0 g of 2-methylimidazolium-1-ethanol (manufactured by Sigma-Aldrich CO. LLC) and 9.2 g of sodium hydride (60%, dispersed in liquid paraffin) (manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 80.0 g of tetrahydrofuran. At room temperature, 14.5 g of iodoethane (manufactured by Showa Chemical Industry Co., Ltd.), dissolved in 80.0 g of tetrahydrofuran, was added dropwise over 30 minutes. The mixture was then heated under reflux at 85 °C for 12 hours.

[0404] Next, 100 ml of water was added to the reaction solution, and the solvent was removed by vacuum distillation. 200 ml of ethanol was added to the residue and stirred at room temperature. The insoluble matter was removed by diatomaceous earth filtration, and the solvent was removed again by vacuum distillation.

[0405] The resulting product was dissolved in 100 ml of pure water, and 38.2 g of anion exchange reagent (hereinafter referred to as "anion raw material") was added. The mixture was stirred at room temperature for one hour. N,N-bis(trifluoromethanesulfonyl)imide lithium (trade name: EF-N115, manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was used as the anion raw material. 100 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 80 g of deionized water.

[0406] Next, ethyl acetate was removed by vacuum distillation to obtain composition C-6. The ionic compound 6 contained in composition C-6 is represented by a combination of structural formulas and anions corresponding to the ionic compounds described in Table 1. Composition C-6 is a solid. The physical properties of composition C-6 are shown in Table 1.

[0407] Composition C-8

[0408] In a nitrogen atmosphere, 15.0 g of imidazole (manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) and 9.2 g of sodium hydride (60%, dispersed in liquid paraffin) (manufactured by Tokyo Chemical Industry Co., Ltd.) were dissolved in 60.0 g of tetrahydrofuran. At room temperature, 60.7 g of 2-bromoethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 80.0 g of tetrahydrofuran was added dropwise over 30 minutes, and the mixture was then heated under reflux at 85 °C for 12 hours.

[0409] Next, 100 ml of water was added to the reaction solution, and the solvent was removed by vacuum distillation. 200 ml of ethanol was added to the residue and stirred at room temperature. The insoluble matter was removed by diatomaceous earth filtration, and the solvent was removed again by vacuum distillation.

[0410] The product obtained was dissolved in 200 ml of pure water, and 27.2 g of potassium N,N-bis(fluorosulfonylimide) (manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.) was added as an anionic raw material. The mixture was stirred at room temperature for 1 hour. 200 ml of ethyl acetate was added to the reaction solution, and the organic layer was washed three times with 120 g of deionized water. Next, the ethyl acetate was removed by vacuum distillation to obtain composition C-8.

[0411] The ionic compound 8 contained in composition C-8 is a compound represented by a combination of structural formulas and anions corresponding to the ionic compounds described in Table 1. The physical properties of composition C-8 are shown in Table 1.

[0412] Composition C-9

[0413] Except for changing the anionic raw materials and their proportions as described in Table 1, composition C-9 was obtained similarly to composition C-8.

[0414] The ionic compound 9 contained in composition C-9 is represented by a combination of structural formulas and anions corresponding to the ionic compounds described in Table 1. The physical properties of composition C-9 are shown in Table 1.

[0415] Composition C-10

[0416] A stir bar was placed in a three-necked flask equipped with a Dimroth condenser. 30 g of 2-pyridineethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) as a tertiary amine, 200 ml (1.25 mol / L) of ethyl acetate, and 79.3 g of N-hydroxyethylbis(trifluoromethanesulfonyl)imide as an ester compound were introduced. The mixture was refluxed under a nitrogen atmosphere for 20 hours. The reaction solution was cooled and separated into ethyl acetate and water. The organic layer was collected, dehydrated with magnesium sulfate, filtered, and dried to obtain composition C-10 containing ionic compound 10. The properties of composition C-10 are shown in Table 1.

[0417] Composition C-11

[0418] A stir bar was placed in a three-necked flask equipped with a Dimroth condenser. 30.0 g of 1-hydroxyethyl-2-hydroxymethylimidazolium as a tertiary amine, 200 mL of 1.25 mol / L ethyl acetate, and 68.7 g of N-methylbis(trifluoromethanesulfonyl)imide as an ester compound were introduced. The mixture was refluxed under a nitrogen atmosphere for 20 hours. The reaction solution was cooled and separated into ethyl acetate and water. The organic layer was collected, dehydrated with magnesium sulfate, filtered, and dried to obtain composition C-11 containing ionic compound 11. The properties of composition C-11 are shown in Table 1.

[0419] Foamed conductive elastic roller

[0420] Manufacturing of foamed conductive elastic roller 1

[0421] A core metal, with an outer diameter of 5 mm and made of stainless steel (SUS304), is placed in a mold as the base material. The mold includes a cylindrical component with an inner diameter of 16.5 mm, an upper mold component, and a lower mold component. A release agent is pre-applied to the inner surface of the mold.

[0422] The following materials (A), (B), (C) and (E)~(I) are blended together, and the urethane composition obtained by blending the materials is injected into the cavity formed in the mold.

[0423] (A): Composition C-1: 3.0 parts by weight

[0424] (B): Polyol A (polyoxyethylene oxypropylene ether triol with a number average molecular weight of 2000; trade name: ACTCOL EP-550N; manufactured by Mitsui Chemicals, Inc.): 60.0 parts by weight

[0425] (C): Polyol B (polyoxyethylene oxypropylene ether triol with a number average molecular weight of 6000, trade name: ACTCOL EP-950P; manufactured by Mitsui Chemicals, Inc.): 40.0 parts by weight

[0426] (E): Polyisocyanate mixture (containing NCO% = 45%, MDI = 20%, trade name: COSMONATE TM20; manufactured by Mitsui Chemicals, Inc.): 24.4 parts by weight

[0427] (F): Silicone foaming stabilizer (trade name: SRX274C, manufactured by Dow Corning Toray Co., Ltd.): 1.0 part by weight

[0428] (G): Tertiary amine catalyst A (a mixture of bis(2-dimethylaminoethyl) ether and dipropylene glycol, trade name: TOYOCAT-ET, manufactured by Tosoh Corporation): 0.3 parts by weight

[0429] (H): Tertiary amine catalyst B (a mixture of triethylenediamine and dipropylene glycol, trade name: TEDA-L33, manufactured by Tosoh Corporation): 0.2 parts by weight

[0430] (I): Foaming agent (water): 1.4 parts by weight

[0431] Subsequently, the mold was heated to 70°C, the urethane rubber composition was foamed and cured for 10 minutes, and the substrate having a foamed elastic layer formed on its outer peripheral surface was removed from the mold. A foamed conductive elastic roller 1 with a foamed conductive elastic layer having a diameter of 16.5 mm on the outer peripheral surface of the substrate was produced. The physical properties of the foamed conductive elastic roller 1 are shown in Table 2.

[0432] Manufacturing of foamed conductive elastic rollers 2-11 and manufacturing of comparative foamed conductive elastic rollers 1-6

[0433] Except for changing the types of compositions and the proportions of polyol A and polyol B as shown in Table 2, foamed conductive elastic rollers 2-11 and comparative foamed conductive elastic rollers 1-6 are manufactured in a similar manner to foamed conductive elastic roller 1. The physical properties of foamed conductive rollers 2-11 and comparative foamed conductive elastic rollers 1-6 are shown in Table 2.

[0434] [Table 2]

[0435]

[0436] In the table, the "difference" in the solubility parameter indicates the difference in solubility parameters between polyurethane and anions.

[0437] The endothermic peak indicates the temperature at which an endothermic peak was observed in the conductive elastic layer using differential scanning calorimetry. An endothermic peak was observed in all rolls at the temperatures shown in Table 2.

[0438] In all foamed conductive elastic rollers 1 to 8 using compositions C-1 to C-3, the polyurethane contained in the foamed conductive elastic layer has a cationic structure represented by the above structural formula (1). In structural formula (1), d1 is 0, Z1 and Z2 are both structures represented by the above structural formula (Z101), and R101 is -C2H4-.

[0439] In all foamed conductive elastic rollers 9 to 11 using compositions C-4 and C-5, the polyurethane contained in the foamed conductive elastic layer has a cationic structure represented by the above structural formula (4). In structural formula (4), d1 is 1; Z2 is the structure represented by the above structural formula (Z101); and R101 is -C2H4-.

[0440] conductive elastic roller

[0441] The following method is used to produce conductive rollers with unfoamed elastic layers.

[0442] Manufacturing of elastic roller D-1

[0443] A primer (trade name: DY35-051; manufactured by Dow Corning Toray Co., Ltd.) was applied to a stainless steel (SUS304) core metal with a diameter of 6 mm and a total length of 278.9 mm, and baked in an oven heated to 180°C for 20 minutes to obtain the substrate. The substrate was placed in a mold, and an addition-cure silicone rubber composition obtained by mixing the following materials was injected into the cavity formed in the mold.

[0444] - Liquid silicone rubber material (trade name SE6724A / B; manufactured by Dow Corning Toray Co., Ltd.): 100 parts by weight

[0445] - Carbon black (trade name: TOKABLACK#4300, manufactured by Tokai Carbon Co., Ltd.): 15 parts by weight

[0446] -Silica powder as a heat-resistant agent: 0.2 parts by weight

[0447] - Platinum catalyst: 0.1 parts by weight

[0448] Subsequently, the mold is heated at 150°C for 15 minutes to vulcanize and cure the silicone rubber. After removing the substrate with the cured silicone rubber layer formed on its outer peripheral surface from the mold, the substrate is further heated at 180°C for 1 hour to complete the curing reaction of the silicone rubber layer. This produces an elastic roller D-1 with a silicone rubber elastic layer with a diameter of 12 mm formed on the outer periphery of the substrate.

[0449] Example of manufacturing isocyanate-terminated prepolymer

[0450] Synthesis of isocyanate-terminated prepolymer B-1

[0451] The reaction vessel was treated with a nitrogen atmosphere, and 38 parts by mass of isocyanate D-1 (polymeric MDI (trade name: Millonate MR200, manufactured by Tosoh Corporation)) were added to the reaction vessel. Next, 100 parts by mass of polyol F-1 (poly(tetramethylene glycol) (trade name: PTMG 2000; manufactured by Mitsubishi Chemical Corporation)) were gradually added dropwise to the reaction vessel, maintaining the temperature in the reaction vessel at 65°C. After the addition was complete, the reaction was carried out at 65°C for 2 hours. The resulting reaction mixture was cooled to room temperature and diluted with 50 parts by mass of methyl ethyl ketone (hereinafter referred to as "MEK") to obtain a solution of isocyanate-terminated prepolymer B-1, wherein the isocyanate group content was 3.4% by mass.

[0452] Manufacturing example of coatings for surface layer formation

[0453] Stir and mix the following materials as a surface layer.

[0454] -Isocyanate-terminated prepolymer B-1: 85 parts by weight

[0455] - Poly(tetramethylene glycol) (trade name: OTMG 2000; manufactured by Mitsubishi Chemical Corporation, hydroxyl value 56 mgKOH / g): 56 parts by weight

[0456] -Composition C-1: 3 parts by weight

[0457] -90 parts by weight of fine urethane resin particles (trade name: Art Pearl C-400; manufactured by Negami Chemical Industrial Co., Ltd.)

[0458] Next, after adding MEK to bring the total solids content to 30% by mass, zirconia beads (center particle diameter 0.8 mm) were injected in such a manner that their mass was twice the mass of the mixture, and the mixture was then mixed using a sand mill with an inner wall made of zirconia. Furthermore, MEK was used to prepare a coating for surface layer formation, achieving a viscosity of 10 cps to 13 cps.

[0459] Manufacturing of conductive elastic roller 12

[0460] A pre-made elastic roller D-1 is immersed in a pre-made coating 1 to form a coating film on the surface of the elastic layer of the elastic roller D-1, and the coating film is dried. By further heat-treating at 160°C for 1 hour, a surface layer with a film thickness of 15 μm is formed on the outer periphery of the elastic layer, thereby manufacturing a conductive elastic roller 12. The physical properties of the conductive elastic roller 12 are shown in Table 3.

[0461] Comparison of the manufacturing of conductive elastic roller 7

[0462] Except for changing composition C-1 to composition C-10, the comparative conductive elastic roller 7 is manufactured in a manner similar to that of the conductive elastic roller 12. The physical properties of the comparative conductive elastic roller 7 are shown in Table 3.

[0463] [Table 3]

[0464]

[0465] Example 1

[0466] Resistance values ​​before and after power-on test

[0467] After placing the foamed conductive elastic roller 1 in a low-temperature, low-humidity environment of 15°C and 10% relative humidity for 24 hours, it was then... Figure 4A and Figure 4B The device shown evaluates the resistance value of the foamed conductive elastic roller 1.

[0468] The following is a summary of the above-described equipment. Note that in the following description, the portion describing a conductive elastic roller can be replaced with a foamed conductive elastic roller.

[0469] like Figure 4AAs shown, non-conductive clamping and adjusting members 41 are installed at both ends of the base 2. In addition, while the conductive base 2 is pressed down by conductive bearings 38 with a load of 4.9N at both ends, a cylindrical metal 37 with a diameter of 30mm is rotated, and a conductive elastic roller 19 is driven to rotate at a speed of 32rpm.

[0470] Next, as Figure 4B As shown, a voltage of -100V is applied using a high-voltage power supply 39, and the potential difference between the two ends of a resistor with a known resistance value (more than two orders of magnitude lower than the resistance value of the conductive elastic roller 19) positioned between the columnar metal 37 and ground is measured. The potential difference is measured using a voltmeter 40 (trade name: 189TRUE RMS MULTIMETER, manufactured by Fluke Corporation).

[0471] Based on the measured potential difference and the resistance value of the resistor, the current flowing through the conductive elastic roller 19 to the columnar metal 37 is calculated. Furthermore, the resistance value of the conductive elastic roller is obtained by dividing the applied voltage of 100V by the resulting current. At this time, a 3-second sampling period is performed starting 2 seconds after the voltage is applied, and the value calculated from the average value is used for the potential difference measurement.

[0472] Using this method, the resistance value of the foamed conductive elastic roller 1 is measured and defined as the resistance value before the energization test.

[0473] Subsequently, a voltage of -100V was applied using the aforementioned equipment, and power was distributed to the driven conductive elastic roller rotating for 2 hours, resulting in a measured resistance value. The measured value was defined as the resistance value of the conductive elastic roller 1 after the energization test. A lower resistance value after the energization test indicates a more satisfactory result. The evaluation results of the foamed conductive elastic roller 1 are shown in Table 4.

[0474] Durability evaluation

[0475] The following describes the image evaluation method.

[0476] A modified LBP-7600C laser printer (manufactured by Canon Inc.), a commercially available model, was used as the electrophotographic image forming device. As a modification point, for evaluation during high-speed processing, the output rate of A4-sized paper was set to 50 sheets per minute. As the processing cartridge, a commercially available developer cartridge 318 (black) (manufactured by Canon Inc.) was used, and the developer supply roller was replaced with a foamed conductive elastic roller 1. The developer filling amount was adjusted to 100g. Note that the yellow, cyan, and magenta cartridges were inserted into the yellow, cyan, and magenta stations respectively, the product toner was removed, and the remaining toner dosage detection mechanism was turned off before evaluation.

[0477] The prepared processing cartridge was installed in the main body of the electrophotographic image forming apparatus and placed in a low-temperature, low-humidity environment of 15°C and 10% relative humidity for 24 hours. Under the same conditions, images were continuously output on A4 evaluation paper (GF-C081, manufactured by Canon Inc.), with the letter "E" at 4 dots and a print percentage of 2% relative to the A4 paper area. This process was repeated until 50,000 sheets were produced. At this point, toner was added when the remaining toner amount decreased to 50g, achieving a toner dosage of 100g. In this way, the decrease in fogging concentration due to changes in the resistance of the conductive elastic roller in a low-temperature, low-humidity environment can be rigorously evaluated.

[0478] At the initial stage of durability testing and after printing 50,000 sheets, solid black images were continuously output on three sheets of paper. The image density of the solid black image was obtained by measuring the image density in the region corresponding to the upper 10% of the first solid black image and the region corresponding to the lower 10% of the third image using a spectrophotometer (trade name: 500 spectrophotometer, manufactured by X-Rite). The difference between the average image density at five points in the region corresponding to the upper 10% and the average image density at five points in the region corresponding to the lower 10% was defined as the evaluation result of solid image tracking. A lower solid image tracking indicates a more satisfactory result. In the initial stage, when the resistance of the conductive elastic roller is high, the solid image tracking value tends to be larger in the initial evaluation. Furthermore, in the evaluation after printing 50,000 sheets, when the resistance of the conductive elastic roller is high after the energization test, the solid image tracking value tends to be larger.

[0479] The evaluation results of the conductive elastic roller are shown in Table 4.

[0480] Examples 2-11

[0481] In Examples 2-11, measurements and evaluations were performed similarly to those in Example 1, except that the conductive elastic rollers were changed to the foamed conductive elastic rollers 2-11 described in Table 2. The evaluation results are shown in Table 4.

[0482] Example 12

[0483] In Example 12, the conductive elastic roller 12 described in Table 3 was used as the developing roller, and the following evaluation was performed.

[0484] Resistance values ​​before and after power-on test

[0485] The resistance values ​​before and after the power-on test were evaluated in a similar manner to Example 1.

[0486] Durability evaluation

[0487] The following section describes the methods for evaluating images.

[0488] A commercially available LBP-7600C laser printer (manufactured by Canon Inc.) was modified as an electrophotographic image forming device. As a modification point, for evaluation during high-speed processing, the output rate of A4-sized paper was set to 50 sheets per minute. As the processing cartridge, a commercially available developer cartridge 318 (black) (manufactured by Canon Inc.) was used, and the developing roller was replaced with a foamed conductive elastic roller 12. At this time, the developer filling amount was adjusted to 100g. Note that the yellow, cyan, and magenta cartridges were inserted into the yellow, cyan, and magenta stations respectively, the product toner was removed, and the remaining toner dosage detection mechanism was turned off before evaluation.

[0489] The prepared processing cartridge was installed in the main body of the electrophotographic image forming apparatus and placed in a low-temperature, low-humidity environment of 15°C and 10% relative humidity for 24 hours. Under the same conditions, images were continuously output on A4 evaluation paper (GF-C081, manufactured by Canon Inc.), with the letter "E" at a size of 4 dots and a print percentage of 2% relative to the A4 paper area. This process was repeated until 50,000 sheets were produced. At this point, toner was refilled when the remaining amount decreased to 50g, achieving a toner dosage of 100g. This method allows for rigorous evaluation of fogging caused by resistance changes in the conductive elastic roller in a low-temperature, low-humidity environment.

[0490] At the initial stage of durability testing and after printing 50,000 sheets of paper, a solid white image is continuously output on three sheets of paper. A reflectance density meter (trade name: TC-6DS / A, manufactured by Tokyo Denshoku Technical Center) is used to measure the reflectance density R1 of the recording material before image formation and the reflectance density R2 on the third recording material after the solid white image has been output. The increase in reflectance density (R2-R1) is defined as the "fogging value" of the developer carrier. As reflectance density, measurements are taken over the entire image printing area of ​​each recording material, and the maximum value is used.

[0491] Note that a lower haze value indicates better quality, and toner typically does not transfer to the transfer paper on which the solid white image is formed. In cases of insufficient developer, during the formation of the solid white image, the developer migrates to the photosensitive element and further transfers to the transfer paper, resulting in an increased haze value. With high initial resistance of the conductive elastic roller, the haze concentration tends to be higher in the initial evaluation. Furthermore, with high resistance of the conductive elastic roller after the energization test, the haze value tends to be higher in the evaluation after printing 50,000 sheets.

[0492] The evaluation results of the conductive elastic roller 12 are shown in Table 5.

[0493] Evaluation of the use of conductive elastic roller 7

[0494] Except for the use of a comparative conductive elastic roller 7 in the evaluation of the conductive elastic roller 12, the evaluation was conducted in a similar manner to the evaluation of the conductive elastic roller. The evaluation results of the comparative conductive elastic roller 7 are shown in Table 5.

[0495] [Table 4]

[0496]

[0497] [Table 5]

[0498]

[0499] Although this disclosure has been described with reference to embodiments, it should be understood that this disclosure is not limited to the disclosed embodiments. The scope of the claims is to be interpreted in the broadest sense to cover all such modifications and equivalent structures and functions.

Claims

1. A conductive elastic roller, comprising: Conductive substrate; and a conductive elastic layer on the substrate, wherein The conductive elastic layer comprises polyurethane containing urethane bonds and ether bonds, and anionic compounds. The polyurethane includes at least one selected from the following cationic structures represented by structural formula (1), the following cationic structures represented by structural formula (2), and the following cationic structures represented by structural formula (3). The anion includes at least one selected from (fluorosulfonyl)imide anion, (fluorosulfonate)imide anion, fluoroborate anion, fluorophosphate anion, dicyandiamide anion, and thiocyanate anion, and The sum of the alkali metal content and the alkaline earth metal content in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g: In structural formula (1), R1 and R2 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 5-membered ring together with each nitrogen atom bonded to R1 and R2, and d1 represents an integer of 0 or 1; Z1 to Z3 each independently represent the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), the structure represented by structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms; however, at least one of Z1 to Z3 is the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), or the structure represented by structural formula (Z103): In structural formula (2), R3 and R4 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 6-membered ring together with each of the nitrogen atoms bonded to R3 and R4, d2 represents an integer greater than or less than 0 and less than 2, and Z5 may be the same or different when d2 is 2; Z4 and Z5 each independently represent the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), the structure represented by structural formula (Z103), or a hydrocarbon group with 1 or more hydrogen atoms and less than 4 carbon atoms; however, at least one of Z4 and Z5 is the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), or the structure represented by structural formula (Z103): In structural formula (3), R5 represents the hydrocarbon group required to form a nitrogen-containing heteroaromatic ring together with the nitrogen atom bonded to R5, and d3 represents an integer of 0 or 1; Z6 and Z7 each independently represent the following structures represented by structural formula (Z101), the following structures represented by structural formula (Z102), the following structures represented by structural formula (Z103), or hydrocarbon groups with 1 or more hydrogen atoms and 4 or fewer carbon atoms; however, at least one of Z6 and Z7 is the following structure represented by structural formula (Z101), the following structure represented by structural formula (Z102), or the following structure represented by structural formula (Z103): In the structural formulas (Z101), (Z102), and (Z103), R101, R102, and R103 each independently represent a straight-chain or branched divalent hydrocarbon group; the symbol "*" represents a bonding portion with a nitrogen atom or carbon atom of a nitrogen-containing heteroaromatic 5-membered ring constituting the structural formula (1), a bonding portion with a nitrogen atom or carbon atom of a nitrogen-containing heteroaromatic 6-membered ring constituting the structural formula (2), or a bonding portion with a nitrogen atom or carbon atom of a nitrogen-containing heteroaromatic ring constituting the structural formula (3); the symbol "**" represents a bonding portion with a carbon atom in the polymer chain of the polyurethane.

2. The conductive elastic roller according to claim 1, wherein, The anion includes at least the bis(fluorosulfonyl)imide anion.

3. The conductive elastic roller according to claim 1 or 2, wherein, The difference between the solubility parameter of the polyurethane and the solubility parameter of the anion is 0.60~2.00 (J / cm). 3 ) 0.5 .

4. The conductive elastic roller according to claim 1 or 2, wherein, The cation structure is represented by the following structural formula (4): In structural formula (4), d1 represents an integer of 0 or 1; Z1 to Z3 each independently represent the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), the structure represented by structural formula (Z103), or a hydrocarbon group with 1 or more hydrogen atoms and 4 or fewer carbon atoms; however, at least one of Z1 to Z3 is the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), or the structure represented by structural formula (Z103).

5. The conductive elastic roller according to claim 1 or 2, wherein, The conductive elastic layer is a foamed conductive elastic layer.

6. The conductive elastic roller according to claim 1 or 2, wherein, The conductive elastic layer is a foamed conductive elastic layer, and The average pore diameter on the surface of the foamed conductive elastic layer is 80~500μm.

7. The conductive elastic roller according to claim 1 or 2, wherein, When the conductive elastic layer is measured by differential scanning calorimetry (DSC), when the temperature is increased from 30°C to 200°C at a heating rate of 10°C / min, at least one endothermic peak exists in the specific heat curve in the range of 40°C to 70°C.

8. A method for manufacturing a conductive elastic roller, The conductive elastic roller includes a conductive substrate and a conductive elastic layer on the substrate; The conductive elastic layer comprises polyurethane containing urethane bonds and ether bonds, as well as anionic compounds. The polyurethane comprises a cationic structure represented by structural formula (1). The anion includes at least one selected from bis(fluorosulfonyl)imide anion and bis(fluorosulfonate)imide anion. The sum of the alkali metal content and the alkaline earth metal content in the conductive elastic layer is 1.0 × 10⁻⁶. -6 Below mol / g; The manufacturing method includes: The step of injecting the elastic layer forming material into a mold in which the substrate is disposed; and The steps of heating the mold and curing the elastic layer forming material to form the conductive elastic layer, wherein... The elastic layer forming material comprises at least a liquid composition containing an ionic compound represented by the following structural formula (7), a polyol, and a polyisocyanate. The liquid composition contains 95% by mass or more and less than 100% by mass of the ionic compound. The liquid composition contains alkali metals and alkaline earth metals at a concentration of less than 30,000 ppm, and The viscosity of the liquid composition at 23°C is 1~1000 mPa·s. In structural formula (1), R1 and R2 represent the hydrocarbon groups required to form a nitrogen-containing heteroaromatic 5-membered ring together with each nitrogen atom bonded to R1 and R2, and d1 represents an integer of 0 or 1; Z1 to Z3 each independently represent the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), the structure represented by structural formula (Z103), or a hydrocarbon group having 1 or more hydrogen atoms and 4 or fewer carbon atoms; however, at least one of Z1 to Z3 is the structure represented by structural formula (Z101), the structure represented by structural formula (Z102), or the structure represented by structural formula (Z103): In structural formulas (Z101), (Z102), and (Z103), R101, R102, and R103 each independently represent a straight-chain or branched divalent hydrocarbon group; the symbol "*" represents a bonding portion with a nitrogen atom or carbon atom of the nitrogen-containing heteroaromatic 5-membered ring constituting structural formula (1); the symbol "**" represents a bonding portion with a carbon atom in the polymer chain of the polyurethane. In structural formula (7), R9 and R10 each independently represent an alkyl group having 1 or more but less than 4 carbon atoms, a hydroxyalkyl group having 1 or more but less than 4 carbon atoms, or a hydrogen atom; at least one of R9 and R10 is a hydroxyalkyl group having 1 or more but less than 4 carbon atoms; X - It represents anion.

9. A processing box configured to be detachably mounted to the main body of an electrophotographic image forming apparatus, the processing box comprising: When the processing box is installed onto the main body, it is a contact member that is electrically connected to the electrical contact point of the main body; developing roller; and a developer supply roller for supplying developer to the developing roller, wherein, The processing cartridge is configured such that a voltage can be applied between the developing roller and the developer supply roller via an electrical connection with the main body. The developer supply roller is a conductive elastic roller according to any one of claims 1 to 7.

10. An electrophotographic image forming apparatus, comprising at least: Electrophotographic photosensitive components; A developing roller disposed in contact with the electrophotographic photosensitive component; as well as A developer supply roller that supplies developer to the developing roller, wherein, The developer supply roller is a conductive elastic roller according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Electrophotographic member, manufacturing method thereof, process cartridge, and electrophotographic apparatus

    JP2016126332A

  • Foam elastic roller, process cartridge and electronic photographic image formation device

    JP2020117578A